Inorganic solid electrolyte-containing composition, sheet for all-solid-state secondary battery, and all-solid-state secondary battery, and manufacturing methods of the latter two

CN116490459BActive Publication Date: 2026-10-27FUJIFILM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202180075811.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-15
Filing Date
2021-12-22
Publication Date
2026-10-27
Estimated Expiration
2041-12-22

AI Technical Summary

Benefits of technology

[0046]本发明能够提供一种分散稳定性及操作性优异的含无机固体电解质组合物,其通过用作全固态二次电池的构成层形成材料,能够实现进一步抑制电池电阻的上升和优异的循环特性。并且,本发明能够提供一种具有由该含无机固体电解质组合物构成的层的全固态二次电池用片材及全固态二次电池。此外,本发明能够提供一种使用该含无机固体电解质组合物的全固态二次电池用片材及全固态二次电池的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116490459B_ABST
    Figure CN116490459B_ABST
Patent Text Reader

Abstract

Provided is an inorganic solid electrolyte-containing composition, a sheet for a full-solid-state secondary battery using the inorganic solid electrolyte-containing composition, a full-solid-state secondary battery, and a method for manufacturing a sheet for a full-solid-state secondary battery and a full-solid-state secondary battery, the inorganic solid electrolyte-containing composition containing an inorganic solid electrolyte, a polymer binder, and a dispersion medium, wherein the polymer binder contains a polymer having a tensile permanent set of less than 50% in a stress-strain curve obtained by repeating stretching and recovery once, and contains the polymer binder having an adsorption rate of less than 60% to the inorganic solid electrolyte in the dispersion medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composition containing an inorganic solid electrolyte, a sheet for an all-solid-state secondary battery, an all-solid-state secondary battery, and a method for manufacturing the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Technology

[0002] All-solid-state secondary batteries have all their components—negative electrode, electrolyte, and positive electrode—made of solids, which significantly improves the safety and reliability of secondary batteries using organic electrolytes. They also extend battery life. Furthermore, all-solid-state secondary batteries can be configured with electrodes and electrolytes directly arranged and connected in series. Therefore, compared to secondary batteries using organic electrolytes, they offer higher energy density and are expected to be used in electric vehicles or large-capacity batteries.

[0003] In such all-solid-state secondary batteries, inorganic solid electrolytes and active materials can be cited as materials forming the constituent layers (solid electrolyte layer, negative electrode active material layer, positive electrode active material layer, etc.). In recent years, inorganic solid electrolytes, especially oxide-based and sulfide-based inorganic solid electrolytes, have attracted attention as electrolyte materials with high ionic conductivity approaching that of organic electrolytes.

[0004] Materials containing the aforementioned inorganic solid electrolytes have been proposed as materials for forming the constituent layer of an all-solid-state secondary battery (constituent layer forming material). For example, Patent Document 1 discloses a solid electrolyte composition containing a block polymer and an inorganic solid electrolyte having conductivity of ions belonging to Group 1 or Group 2 of the periodic table, wherein the block polymer contains at least one block composed of repeating units having at least one functional group having an affinity for the electrode active material or the inorganic solid electrolyte. Furthermore, Patent Document 2 discloses a block copolymer and a slurry containing an electrode active material, wherein the block copolymer has: segment A, a structural unit containing a vinyl monomer having an acid component; segment B, a structural unit containing an alkyl (meth)acrylate monomer; and segment C, a structural unit containing a vinyl monomer with a glass transition temperature of 80°C or higher, wherein the content of segment C is 20 to 50% by mass.

[0005] Previous technical documents

[0006] Patent documents

[0007] Patent Document 1: International Publication No. 2017 / 030154

[0008] Patent Document 2: Japanese Patent No. 5617725 Summary of the Invention

[0009] The technical problem to be solved by the invention

[0010] Because the constituent layers of an all-solid-state secondary battery are formed by solid particles (inorganic solid electrolyte, active material, conductive additives, etc.), the interfacial contact between these particles is limited, leading to an increase in interfacial resistance (reduced ionic conductivity). Furthermore, the solid particles cannot achieve sufficient adhesion to each other. This increase in interfacial resistance (increased battery resistance) not only reduces ionic conductivity but also degrades cycle performance. Therefore, the insufficient adhesion between solid particles further reduces cycle performance.

[0011] The increase in resistance, which is the main cause of battery performance degradation, is not only due to the interfacial contact state between solid particles, but also to the uneven presence (configuration) of solid particles in the constituent layer, and even the surface flatness of the constituent layer. Therefore, when a constituent layer is formed from a constituent layer forming material, the constituent layer forming material is required not only to have good dispersion of the solid particles after preparation, but also to have the property of stably maintaining the dispersion of the solid particles after preparation (dispersion stability) and having appropriate viscosity and the property of forming a good coating film with high flowability (operability).

[0012] However, patent documents 1 and 2 did not conduct research based on this viewpoint. Moreover, in recent years, research and development on the high performance and practical application of electric vehicles has progressed rapidly, leading to increasingly higher requirements for the battery performance (e.g., conductivity, cycle characteristics) of all-solid-state rechargeable batteries.

[0013] The objective of this invention is to provide an inorganic solid electrolyte composition with excellent dispersion stability and operability, which, when used as a constituent layer forming material in an all-solid-state secondary battery, can further suppress the rise in battery resistance and achieve excellent cycle characteristics. Furthermore, the objective of this invention is to provide an all-solid-state secondary battery sheet using the inorganic solid electrolyte composition, an all-solid-state secondary battery, and a method for manufacturing the all-solid-state secondary battery sheet and the all-solid-state secondary battery.

[0014] means for solving technical problems

[0015] The inventors have conducted various studies on polymer binders used in conjunction with solid particles such as inorganic solid electrolytes and dispersion media. They have discovered that a polymer binder containing a polymer exhibiting a low adsorption rate of less than 60% relative to the inorganic solid electrolyte in the dispersion media, formed by repeatedly stretching and recovering the polymer and showing a tensile permanent deformation of less than 50% in the stress-strain curve, can ensure sufficient interfacial contact between solid particles in the constituent layer and firmly bond them together while maintaining excellent dispersion stability and operability of the composition. Consequently, it has been found that by using this inorganic solid electrolyte-containing composition as a constituent layer forming material, a constituent layer that suppresses the increase in interfacial resistance between solid particles while firmly bonding the solid particles together can be formed, and an all-solid-state secondary battery capable of achieving both increased battery resistance and excellent cycle characteristics can be manufactured.

[0016] Based on these insights, the present invention underwent further and repeated research, thereby completing the present invention.

[0017] That is, the above-mentioned problems are solved through the following solutions.

[0018] <1> A composition containing an inorganic solid electrolyte, comprising an inorganic solid electrolyte having conductive ions of metals belonging to Group 1 or Group 2 of the periodic table, a polymer binder PB, and a dispersion medium, wherein,

[0019] The polymer binder PB comprises a polymer P1 whose tensile permanent deformation in the stress-strain curve obtained by repeated stretching and recovery is less than 50%, and comprises a polymer binder PB1 whose adsorption rate of the inorganic solid electrolyte in the dispersion medium is less than 60%.

[0020] <2> According to the inorganic solid electrolyte composition described in <1>, wherein,

[0021] The permanent tensile deformation is less than 25%.

[0022] <3> The inorganic solid electrolyte composition according to <1> or <2>, wherein,

[0023] Polymer P1 has an elongation at break of over 400%.

[0024] <4> The inorganic solid electrolyte composition according to any one of <1> to <3>, wherein,

[0025] Polymer P1 comprises constituents having functional groups selected from the functional group (a) below.

[0026] <Functional Groups (a)>

[0027] Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, ether bond, imino, ester bond, amide bond, carbamate bond, thiocarbamate bond, urea bond, thiourea bond, heterocyclic group, aryl, carboxylic anhydride group, fluoroalkyl, siloxane, carbonate bond, ketone bond

[0028] <5> According to the inorganic solid electrolyte composition described in <4>, wherein,

[0029] The content of the above-mentioned components in polymer P1 is 0.1 to 20% by mass.

[0030] <6> The inorganic solid electrolyte composition according to any one of <1> to <5>, wherein the polymer P1 is a block polymer.

[0031] <7> An inorganic solid electrolyte composition according to any one of <1> to <6>, wherein the polymer P1 comprises a component derived from a (meth)acrylate compound.

[0032] <8> The inorganic solid electrolyte composition according to any one of <1> to <7>, wherein,

[0033] Polymer P1 is a block polymer having at least segment A and segment B, wherein segment A comprises constituents derived from vinyl compounds or (meth)acrylate compounds with a glass transition temperature of 50°C or higher, and segment B comprises constituents derived from (meth)acrylate compounds with a glass transition temperature of 15°C or lower.

[0034] <9> The inorganic solid electrolyte composition according to any one of <1> to <8>, wherein,

[0035] Polymer adhesive PB also includes chain polymer adhesive PB3, which is composed of (meth)acrylic acid polymer.

[0036] <10> An inorganic solid electrolyte composition according to any one of <1> to <9>, wherein the composition contains an active substance.

[0037] <11> The inorganic solid electrolyte composition according to any one of <1> to <10> contains a conductive aid.

[0038] <12> The inorganic solid electrolyte composition according to any one of <1> to <11>, wherein,

[0039] Inorganic solid electrolytes are sulfide-based inorganic solid electrolytes.

[0040] <13> A sheet for an all-solid-state secondary battery, having a layer composed of an inorganic solid electrolyte composition as described in any one of <1> to <12> above.

[0041] <14> An all-solid-state secondary battery, which sequentially comprises a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein,

[0042] At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer composed of an inorganic solid electrolyte composition as described in any one of <1> to <12> above.

[0043] <15> A method for manufacturing a sheet for an all-solid-state secondary battery, wherein the inorganic solid electrolyte composition described in any one of <1> to <12> is used to form a film.

[0044] <16> A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is manufactured by the manufacturing method described in <15> above.

[0045] Invention Effects

[0046] This invention provides an inorganic solid electrolyte composition with excellent dispersion stability and operability. By using it as a constituent layer forming material in an all-solid-state secondary battery, it further suppresses the rise in battery resistance and achieves excellent cycle characteristics. Furthermore, this invention provides an all-solid-state secondary battery sheet having a layer composed of this inorganic solid electrolyte composition and an all-solid-state secondary battery. In addition, this invention provides a method for manufacturing the all-solid-state secondary battery sheet using the inorganic solid electrolyte composition and the all-solid-state secondary battery.

[0047] The above-described features and other features and advantages of the present invention will become more apparent from the accompanying drawings and from the following description. Attached Figure Description

[0048] Figure 1 This is a longitudinal sectional view illustrating a preferred embodiment of the all-solid-state secondary battery of the present invention.

[0049] Figure 2 This is a schematic longitudinal sectional view of the button-shaped all-solid-state secondary battery manufactured in the embodiment.

[0050] Figure 3 This is a diagram showing an example of a stress-strain curve obtained in the determination of tensile permanent deformation. Detailed Implementation

[0051] In this invention, the numerical range indicated by "~" refers to the range encompassed by the values ​​recorded before and after "~" as the lower and upper limits. Furthermore, in this invention, when multiple numerical ranges are defined for the content, physical properties, etc., of a component, the upper and lower limits forming the numerical range are not limited to a specific combination recorded before and after "~" as a specific numerical range, but can be defined as a numerical range formed by appropriately combining the upper and lower limits of each numerical range.

[0052] In this invention, the designation of a compound (e.g., when referred to as a compound by appending a compound at the end) means that in addition to the compound itself, it also includes its salt and its ions. Furthermore, it refers to derivatives that include modifications to the introduced substituents or other components without impairing the effects of this invention.

[0053] In this invention, (meth)acrylic acid refers to one or both of acrylic acid and methacrylic acid. The same applies to (meth)acrylates.

[0054] In this invention, the term "substituent, linking group, etc." (hereinafter referred to as "substituent, etc.") that is not explicitly stated as substituted or unsubstituted means that the group may also have suitable substituents. Therefore, in this invention, even when simply described as a YYY group, the YYY group includes not only those without substituents but also those with substituents. This also applies to compounds where substitution or unsubstituent is not explicitly stated. As a preferred substituent, substituent Z, described later, can be cited as an example.

[0055] In this invention, when multiple substituents, etc., are represented by specific symbols, or when multiple substituents, etc., are specified simultaneously or selectively, it means that each substituent, etc., may be the same as or different from each other. Furthermore, even if not specifically stated, when multiple substituents, etc., are adjacent, it means that they may be linked together or fused together to form a ring.

[0056] In this invention, "polymer" refers to a polymer, but it has the same meaning as "high molecular weight compound." Furthermore, "polymer adhesive" (also simply "adhesive") refers to an adhesive composed of polymers, including the polymer itself and adhesives formed containing polymers.

[0057] [Inorganic solid electrolyte composition]

[0058] The inorganic solid electrolyte composition of the present invention contains an inorganic solid electrolyte having conductivity of ions of metals belonging to Group 1 or Group 2 of the periodic table, a polymer binder PB, and a dispersion medium.

[0059] As described later, the polymer binder PB includes one or two low-adsorption binders PB1 that exhibit an adsorption rate of less than 60% relative to the inorganic solid electrolyte in the dispersion medium contained in the inorganic solid electrolyte composition. The low-adsorption binder PB1 is only required to be present in the inorganic solid electrolyte composition (dispersion medium), and its state of presence is not particularly limited. For example, the low-adsorption binder PB1 may not adsorb onto the inorganic solid electrolyte in the inorganic solid electrolyte composition, but it is preferable to have the function of adsorbing onto solid particles and dispersing in the dispersion medium.

[0060] The low-adsorption binder PB1 may or may not have the function of binding solid particles together in an inorganic solid electrolyte composition, but at least in the layer formed from the inorganic solid electrolyte composition, it has the function of binding solid particles such as inorganic solid electrolytes (and, in addition, coexisting active substances, conductive additives) together (e.g., inorganic solid electrolytes together, inorganic solid electrolytes and active substances, active substances together) (acting as a binder). Furthermore, it also functions as a binder for bonding current collectors and solid particles.

[0061] The inorganic solid electrolyte composition of the present invention is preferably a slurry formed by dispersing inorganic solid electrolytes in a dispersion medium.

[0062] The inorganic solid electrolyte composition of the present invention exhibits excellent dispersion stability and operability. By using this inorganic solid electrolyte composition as a constituent layer forming material, it is possible to realize a sheet for an all-solid-state secondary battery with a low-resistance constituent layer having a firmly bonded solid particle structure, and further, to realize an all-solid-state secondary battery with low resistance and excellent cycle characteristics. Furthermore, in the method of forming the active material layer on the current collector using the inorganic solid electrolyte composition of the present invention, a strong adhesion between the current collector and the active material layer can be achieved, and cycle characteristics can be further improved.

[0063] The detailed reasons are not yet clear, but are believed to be as follows: It is believed that the low-adsorption binder PB1, which exhibits an adsorption rate of less than 60% relative to the inorganic solid electrolyte, does not excessively adsorb onto the inorganic solid electrolyte in the composition containing the inorganic solid electrolyte. This inhibits the re-aggregation or precipitation of the inorganic solid electrolyte not only immediately after preparation but also over time. Therefore, it can stably maintain a high degree of dispersibility immediately after preparation (excellent dispersion stability) and also suppress excessive viscosity increase while exhibiting good flowability (excellent operability).

[0064] When the inorganic solid electrolyte composition of the present invention, exhibiting such excellent dispersion stability and flowability, is used to form the constituent layer, the solid particles in the constituent layer can be in direct contact with each other, thereby creating sufficient conduction pathways. Furthermore, even during film formation of the inorganic solid electrolyte composition (e.g., during coating, and even during drying), agglomeration or precipitation of solid particles can be suppressed, and the distribution of solid particles in the constituent layer can be homogenized. Moreover, during film formation, especially during coating, the inorganic solid electrolyte composition flows appropriately (smoothly), without surface roughness due to insufficient or excessive flow, and without surface roughness caused by blockage at the dispensing portion during coating, resulting in a constituent layer with excellent surface properties (excellent surface properties of the coated surface). Consequently, the increase in interfacial resistance between solid particles and the resistance of the constituent layer can be suppressed. Moreover, the low-adsorption adhesive PB1, as described below, contains a polymer with a tensile permanent deformation of less than 50%. Therefore, in the constituent layers, even in the face of external stresses such as vibration or bending, and consequently in the expansion and contraction of the constituent layers caused by charging and discharging, it is possible to bond solid particles together with a sufficiently strong adhesive force.

[0065] Thus, the inorganic solid electrolyte composition of the present invention can form a low-resistance structural layer in which solid particles are firmly bonded together. Furthermore, it is believed that an all-solid-state secondary battery with this structural layer is less prone to overcurrent during charging and discharging, preventing degradation of solid particles, and maintaining a strong bond between solid particles even with repeated charging and discharging. Therefore, it is possible to realize an all-solid-state secondary battery that does not experience a significant decrease in battery characteristics even with repeated charging and discharging, exhibits excellent cycle characteristics, and displays high conductivity (ionic conductivity and electronic conductivity).

[0066] When the inorganic solid electrolyte composition of the present invention, which exhibits excellent dispersion stability and operability, is used to form an active material layer on the current collector, a strong bond between the current collector and the active material can be achieved. Therefore, the all-solid-state secondary battery in which the active material layer of the present invention is formed on the current collector enhances the bond between the current collector and the active material, and can further improve cycle characteristics and conductivity.

[0067] The inorganic solid electrolyte composition of the present invention can be preferably used as a forming material (constituent layer forming material) for sheets (including electrode sheets for all-solid-state secondary batteries) or solid electrolyte layers or active material layers of all-solid-state secondary batteries. In particular, it can be preferably used as a forming material for negative electrode sheets or negative electrode active material layers of all-solid-state secondary batteries containing negative electrode active materials that expand and contract significantly due to charging and discharging, in which high cycle characteristics and high conductivity can also be achieved.

[0068] The inorganic solid electrolyte composition of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition includes not only being free of water but also having a water content (also referred to as moisture content) preferably of 500 ppm or less. In the non-aqueous composition, the water content is more preferably 200 ppm or less, further preferably 100 ppm or less, and particularly preferably 50 ppm or less. If the inorganic solid electrolyte composition is a non-aqueous composition, the degradation of the inorganic solid electrolyte can be suppressed. The water content refers to the amount of water contained in the inorganic solid electrolyte composition (relative to the mass ratio of the inorganic solid electrolyte composition), specifically, it is defined as the value obtained by filtration using a 0.02 μm membrane filter and determination using Karl Fischer titration.

[0069] In addition to containing an inorganic solid electrolyte, the inorganic solid electrolyte composition of the present invention also includes, in the form of, an active substance and a conductive additive (the composition in this manner is referred to as an electrode composition).

[0070] The components contained in the inorganic solid electrolyte composition of the present invention and the components that may be contained therein will be described below.

[0071] <Inorganic Solid Electrolytes>

[0072] The inorganic solid electrolyte composition of the present invention contains an inorganic solid electrolyte.

[0073] In this invention, inorganic solid electrolyte refers to an inorganic solid electrolyte, which is a solid electrolyte capable of allowing ions to move within it. It is clearly distinguished from organic solid electrolytes (such as polymeric electrolytes represented by polyethylene oxide (PEO) and organic electrolyte salts represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)) from the perspective of not containing organic materials as the primary ion-conducting material. Furthermore, since inorganic solid electrolytes are solid in their stable state, they generally do not dissociate or ionize into cations and anions. In this respect, they are clearly distinguished from inorganic electrolyte salts (such as LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), and LiCl) that dissociate or ionize into cations and anions in electrolytes or polymers. There are no particular limitations as long as the inorganic solid electrolyte possesses the ion conductivity of metals belonging to Group 1 or Group 2 of the periodic table; it generally does not possess electronic conductivity. In the case of the all-solid-state secondary battery of the present invention being a lithium-ion battery, it is preferable that the inorganic solid electrolyte has the ionic conductivity of lithium ions.

[0074] The aforementioned inorganic solid electrolyte can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as inorganic solid electrolytes, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based inorganic solid electrolytes can be mentioned. From the viewpoint of forming a better interface between the active material and the inorganic solid electrolyte, sulfide-based inorganic solid electrolytes are preferred.

[0075] (i) Sulfide-based inorganic solid electrolytes

[0076] The preferred form is a sulfide-based inorganic solid electrolyte containing sulfur atoms, exhibiting ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and possessing electronic insulation properties. The preferred sulfide-based inorganic solid electrolyte contains at least Li, S, and P as elements and exhibits lithium-ion conductivity; however, it may contain other elements besides Li, S, and P, depending on the purpose or circumstances.

[0077] As a sulfide-based inorganic solid electrolyte, for example, a lithium-ion conductive inorganic solid electrolyte that satisfies the composition represented by the following formula (S1) can be cited.

[0078] L a1 M b1 P c1 S d1 A e1 (S1)

[0079] In the formula, L represents an element selected from Li, Na, and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge. A represents an element selected from I, Br, Cl, and F. a1 to e1 represent the composition ratio of each element, where a1:b1:c1:d1:e1 satisfies 1–12:0–5:1:2–12:0–10. a1 is preferably 1–9, more preferably 1.5–7.5. b1 is preferably 0–3, more preferably 0–1. d1 is preferably 2.5–10, more preferably 3.0–8.5. e1 is preferably 0–5, more preferably 0–3.

[0080] As described below, the composition ratio of each element can be controlled by adjusting the amount of raw material compounds used in the manufacture of sulfide-based inorganic solid electrolytes.

[0081] Sulfide-based inorganic solid electrolytes can be amorphous (glass), crystallized (glass-ceramic), or partially crystallized. For example, Li-PS type glasses or Li-PS type glass-ceramics containing Li, P, and S can be used.

[0082] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two of the following raw materials: lithium sulfide (Li2S), phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)), monomeric phosphorus, monomeric sulfur, sodium sulfide, hydrogen sulfide, lithium halides (e.g., LiI, LiBr, LiCl), and sulfides of the elements represented by M above (e.g., SiS2, SnS, GeS2).

[0083] The ratio of Li₂S to P₂S₅ in Li-PS glass and Li-PS glass-ceramics is preferably 60:40 to 90:10, more preferably 68:32 to 78:22, in terms of the molar ratio of Li₂S:P₂S₅. Setting the Li₂S to P₂S₅ ratio within this range improves lithium-ion conductivity. Specifically, the lithium-ion conductivity is preferably set to 1 × 10⁻⁶. -4 S / cm or higher, more preferably 1×10 -3 S / cm or higher. Although no specific upper limit is set, it is actually 1×10⁻⁶. -1 Below S / cm.

[0084] As specific examples of sulfide-based inorganic solid electrolytes, combinations of raw materials are illustrated below. For example, Li₂S-P₂S₅, Li₂S-P₂S₅-LiCl, Li₂S-P₂S₅-H₂S, Li₂S-P₂S₅-H₂S-LiCl, Li₂S-LiI-P₂S₅, Li₂S-LiI-Li₂O-P₂S₅, Li₂S-LiBr-P₂S₅, Li₂S-Li₂O-P₂S₅, Li₂S-Li₃PO₄-P₂S₅, Li₂S-P₂S₅-P₂O₅, Li₂S-P₂S₅-SiS₂, Li₂S-P₂S₅-SiS₂-LiCl, Li₂S-P₂S₅-SnS, and Li₂S-P₂S₅-Al₂ can be cited. S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12And so on. The mixing ratio of each raw material is not limited. As a method for synthesizing sulfide-based inorganic solid electrolyte materials using this raw material composition, for example, an amorphization method can be mentioned. As an amorphization method, examples include mechanical polishing, solution processing, and melt quenching. Processing at room temperature is possible, thereby simplifying the manufacturing process.

[0085] (ii) Oxide-based inorganic solid electrolytes

[0086] Oxide-based inorganic solid electrolytes are preferably compounds containing oxygen atoms, possessing ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.

[0087] For oxide-based inorganic solid electrolytes, the preferred ionic conductivity is 1×10⁻⁶. -6 S / cm or higher, preferably 5×10 -6 S / cm or higher, especially preferably 1×10 -5 S / cm or higher. Although there is no specific upper limit, it is actually 1×10 -1 Below S / cm.

[0088] As a specific example of a compound, Li can be cited. xa La ya TiO3 [xa satisfies 0.3≤xa≤0.7, ya satisfies 0.3≤ya≤0.7.] (LLT); Li xb La yb Zr zb M bb mb O nb (M bb It consists of one or more elements selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn. xb satisfies 5 ≤ ​​xb ≤ 10, yb satisfies 1 ≤ yb ≤ 4, zb satisfies 1 ≤ zb ≤ 4, mb satisfies 0 ≤ mb ≤ 2, and nb satisfies 5 ≤ ​​nb ≤ 20. Li xc B yc M cc zc O nc (M cc It is an element selected from C, S, Al, Si, Ga, Ge, In, and Sn. xc satisfies 0 < xc ≤ 5, yc satisfies 0 < yc ≤ 1, zc satisfies 0 < zc ≤ 1, and nc satisfies 0 < nc ≤ 6. ); Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd(xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, nd satisfies 3≤nd≤13.) ; Li (3-2xe) M ee xe D ee O(xe) represents a number greater than 0 and less than 0.1, M ee This represents a divalent metal atom. (D) ee This represents a halogen atom or a combination of two or more halogen atoms. (Li) xf Si yf O zf (xf satisfies 1 ≤ xf ≤ 5, yf satisfies 0 < yf ≤ 3, zf satisfies 1 ≤ zf ≤ 10.) ; Li xg S yg O zg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, zg satisfies 1≤zg≤10.) ; Li3BO3; Li3BO3-Li2SO4; Li2O-B2O3-P2O5; Li2O-SiO2; Li6BaLa2Ta2O 12 Li3PO (4-3 / 2w) N w (w satisfies w < 1); Li has a LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La with a perovskite-type crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O with a NASICON (Natrium super ionic conductor) crystal structure 12 Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0≤xh≤1, yh satisfies 0≤yh≤1); Li7La3Zr2O has a garnet-type crystal structure. 12 (LLZ) etc.

[0089] Furthermore, phosphorus compounds containing Li, P, and O are preferred. Examples include lithium phosphate (Li3PO4); LiPON, in which nitrogen element replaces a portion of the oxygen element in lithium phosphate; and LiPOD. 1 (D 1Preferably, it contains one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, and Au.

[0090] Furthermore, LiA can be preferably used. 1 ON(A 1 It consists of one or more elements selected from Si, B, Ge, Al, C, and Ga.

[0091] (iii) Halogenated inorganic solid electrolytes

[0092] Halogen-based inorganic solid electrolytes are preferably compounds containing halogen atoms, possessing ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.

[0093] There are no particular limitations on the type of inorganic solid electrolyte, such as LiCl, LiBr, LiI, and compounds like Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among these, Li3YBr6 and Li3YCl6 are preferred.

[0094] (iv) Hydride-based inorganic solid electrolytes

[0095] Hydride-based inorganic solid electrolytes are preferably compounds containing hydrogen atoms, possessing ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.

[0096] There are no particular limitations for hydride-based inorganic solid electrolytes; examples include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.

[0097] The inorganic solid electrolyte is preferably a particle. In this case, the particle size (volume average particle size) of the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.1 μm or more. As an upper limit, it is preferably 100 μm or less, more preferably 50 μm or less.

[0098] The particle size of the inorganic solid electrolyte was determined using the following steps. A 1% (w / w) dispersion of the inorganic solid electrolyte particles was prepared by diluting the particles with water (or heptane if water is unstable) in a 20 mL sample vial. The diluted dispersion sample was then irradiated with ultrasound at 1 kHz for 10 minutes and immediately used in the test. Using this dispersion sample, 50 data acquisitions were performed using a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.) at 25°C using a measuring quartz cell to obtain the volume average particle size. Other detailed conditions were referenced as needed in Japanese Industrial Standard (JIS) Z8828:2013 "Particle Size Analysis - Dynamic Light Scattering Method". Five samples were prepared for each grade, and their average value was used.

[0099] Inorganic solid electrolytes may contain one or more types.

[0100] There is no particular limitation on the content of inorganic solid electrolyte in the inorganic solid electrolyte composition. From the viewpoint of adhesion, and further from the viewpoint of dispersibility, it is preferable that the solid content is 50% by mass or more, more preferably 70% by mass or more, and especially preferably 90% by mass or more out of 100% by mass. As an upper limit, from the same viewpoint, it is preferable that it is 99.9% by mass or less, more preferably 99.5% by mass or less, and especially preferably 99% by mass or less.

[0101] However, when the inorganic solid electrolyte composition contains the active substance described later, the total content of the active substance and the inorganic solid electrolyte in the inorganic solid electrolyte composition is preferably within the range described above.

[0102] In this invention, solid components refer to those components that, when dried at 150°C for 6 hours under a nitrogen atmosphere and at a pressure of 1 mmHg, volatilize or evaporate without disappearing. Typically, this refers to components other than the dispersion medium described later.

[0103] <Polymer Adhesives PB>

[0104] The inorganic solid electrolyte composition of the present invention contains a polymer binder PB. The polymer binder PB contained in the inorganic solid electrolyte composition of the present invention comprises a polymer P1 with a tensile permanent deformation of less than 50% (described later), and comprises one or more polymer binders (low-adsorption binders) PB1 with an adsorption rate of less than 60% relative to the inorganic solid electrolyte in the composition.

[0105] Furthermore, the polymer binder PB contained in the inorganic solid electrolyte composition may include one or more polymer binders other than the low-adsorption binder PB1. As for the polymer binder other than the low-adsorption binder PB1, there are no particular limitations as long as it does not satisfy at least one of the following: tensile permanent deformation of the polymer and adsorption rate of the binder. Examples include the particulate binder PB2 (preferably a particulate binder with an adsorption rate of 60% or more relative to the inorganic solid electrolyte in the composition), chain polymer binder PB3, and high-adsorption binder with an adsorption rate of 60% or more relative to the inorganic solid electrolyte in the composition. There are no particular limitations on the tensile permanent deformation of the polymers constituting the particulate binder PB2, chain polymer binder PB3, high-adsorption binder, etc., but it is preferably unmeasurable or 50% or more.

[0106] (Low-adsorption adhesive PB1)

[0107] The adsorption rate shown by the low-adsorption binder PB1 is a value determined using the inorganic solid electrolyte contained in the composition containing the inorganic solid electrolyte and the dispersion medium, and is an indicator of the degree to which the binder in the dispersion medium is adsorbed onto the inorganic solid electrolyte. Here, the adsorption of the binder relative to the inorganic solid electrolyte includes not only physical adsorption but also chemical adsorption (adsorption through the formation of chemical bonds, adsorption through electron donation and acceptance, etc.).

[0108] When the inorganic solid electrolyte composition contains multiple inorganic solid electrolytes, the adsorption rate is defined as the adsorption rate relative to inorganic solid electrolytes having the same composition (type and content) as those in the inorganic solid electrolyte composition. When the inorganic solid electrolyte composition contains multiple dispersion media, the adsorption rate is also determined using dispersion media having the same composition (type and content) as those in the inorganic solid electrolyte composition. Furthermore, when multiple low-adsorption binders PB1 are used, the adsorption rate is defined as the adsorption rate relative to the multiple low-adsorption binders PB1, similar to the method used with inorganic solid electrolyte compositions.

[0109] In this invention, the adsorption rate of the low-adsorption adhesive PB1 is set as a value calculated by the method described in the examples.

[0110] In this invention, the adsorption rate of inorganic solid electrolytes can be appropriately set according to the type of polymer P1 (structure and composition of polymer chain) that forms the low-adsorption binder PB1, the type or content of functional groups selected from the functional group (a) described later, and the morphology of the low-adsorption binder PB1 (solution amount in dispersion medium).

[0111] In addition, the adsorption rate of polymer adhesives other than the low-adsorption adhesive PB1 is also set to the value calculated by the same method as the low-adsorption adhesive PB1.

[0112] The adsorption rate of the low-adsorption binder PB1 is less than 60%. If the low-adsorption binder PB1 exhibits the aforementioned adsorption rate, it can suppress excessive adsorption of the inorganic solid electrolyte and improve the dispersion stability and workability (sometimes collectively referred to as dispersion characteristics) of the composition containing the inorganic solid electrolyte. From the viewpoint of achieving a higher level of dispersion characteristics, the adsorption rate is preferably 40% or less, more preferably 30% or less, further preferably 20% or less, and particularly preferably 10% or less. On the other hand, there is no particular limitation on the lower limit of the adsorption rate, and it can also be set to 0%. From the viewpoint of dispersion characteristics, the lower limit of the adsorption rate is preferably small; on the other hand, from the viewpoint of improving the adhesion of the inorganic solid electrolyte, it is preferably 0.1% or more, more preferably 1% or more.

[0113] In the case where the inorganic solid electrolyte composition of the present invention contains the active material described later, there is no particular limitation on the adsorption rate of the low-adsorption binder PB1 on the active material.

[0114] A preferred characteristic of the low-adsorption binder PB1 is its solubility relative to the dispersion medium contained in the inorganic solid electrolyte composition. While the amount of low-adsorption binder PB1 in the inorganic solid electrolyte composition depends on its content, it is generally preferred to be present in the inorganic solid electrolyte composition in a state of dissolution in the dispersion medium. Thus, the low-adsorption binder PB1 stably functions to disperse solid particles in the dispersion medium, thereby improving the dispersion characteristics of the inorganic solid electrolyte composition.

[0115] In this invention, the way in which the low-adsorption binder PB1 dissolves in the dispersion medium in the inorganic solid electrolyte composition is not limited to all ways in which the low-adsorption binder PB1 dissolves in the dispersion medium. For example, if the solubility of the low-adsorption binder PB1 is 50% or more relative to the dispersion medium, a portion of the low-adsorption binder PB1 may be insoluble in the inorganic solid electrolyte composition.

[0116] The method for determining solubility is as follows: Accurately weigh 0.1 g of the low-adsorption binder (the test object), and denote the accurate weighed mass as W0. Next, accurately weigh 10 g of the low-adsorption binder and dispersion medium into a container, and mix using a mixing rotor (model VMR-5, manufactured by AS ONE Corporation) at 25°C and 100 rpm for 48 hours. Then, filter the insoluble matter from the solution, vacuum dry the resulting solid at 120°C for 3 hours, and accurately weigh the mass of this insoluble matter as W1. Based on the accurately weighed W0 and W1, calculate the solubility (%) in the dispersion medium according to the following formula.

[0117] Solubility (%) = (W0 - W1) / W0 × 100

[0118] When the low-adsorption binder PB1 is in particulate form (where the dispersion medium contained in the inorganic solid electrolyte composition does not exhibit solubility), its shape is not particularly limited and can be flat, amorphous, etc., but spherical or granular is preferred. In this case, the average particle size of the particulate low-adsorption binder in the inorganic solid electrolyte composition is not particularly limited, but is preferably 1 nm or more, more preferably 10 nm or more, and even more preferably 30 nm or more. As an upper limit, it is preferably 5 μm or less, more preferably 1 μm or less. The average particle size of the low-adsorption binder can be measured in the same way as the particle size of the inorganic solid electrolyte. The average particle size of the low-adsorption binder can be adjusted, for example, by the type of dispersion medium, the composition of the binder-forming polymer, etc.

[0119] -Polymer P1 contained in the low-adsorption adhesive PB1-

[0120] The low-adsorption binder PB1 is formed by comprising a polymer P1 with a tensile permanent deformation of less than 50%. The polymer P1 contained in the low-adsorption binder PB1 (also referred to as the binder-forming polymer) is a polymer P1 that imparts the aforementioned adsorption rate relative to the inorganic solid electrolyte to the low-adsorption binder PB1, and whose tensile permanent deformation in the stress-strain curve obtained by repeated stretching and recovery once is less than 50%. When polymer P1 with a tensile permanent deformation of less than 50% is included in the polymer binder PB1, as described above, it is possible to maintain the excellent dispersion stability and improved workability of the low-adsorption binder PB1 while firmly bonding (adhering) solid particles together to form a highly conductive (low-resistance) and robust constituent layer, while constructing sufficient conductive pathways.

[0121] From the viewpoint of maintaining dispersion stability and workability, and further improving conductivity and adhesion, the tensile permanent deformation of the adhesive-forming polymer P1 is preferably 40% or less, more preferably 25% or less, even more preferably 20% or less, and particularly preferably 15% or less. On the other hand, there is no particular limitation on the lower limit of tensile permanent deformation, but the smaller the better, practically 0%.

[0122] The tensile permanent deformation of the adhesive-forming polymer P1 is determined by stretching and restoring a test piece formed of the adhesive-forming polymer to a specified elongation to create a stress-strain curve, and calculating the value based on the stress-strain curve. Specifically, the value is set to be determined (calculated) by the method described in the examples.

[0123] In this invention, the tensile permanent deformation can be appropriately set according to the type of binder-forming polymer P1 (structure and composition of the polymer chain) or the bonding mode of the main chain, the glass transition temperature, molecular weight distribution, stereoregularity, etc. of the binder-forming polymer P1. A preferred adjustment method is to reduce the content of blocks with high glass transition temperatures and narrow the molecular weight distribution of the block polymer, based on using the binder-forming polymer P1 as a block polymer, thereby reducing the tensile permanent deformation.

[0124] In addition, the tensile permanent deformation of the polymer forming the polymer adhesive other than the low-adsorption adhesive PB1 is also set to the value calculated by the same method as that used for the adhesive forming polymer P1.

[0125] The adhesive forming polymer P1 only needs to exhibit the tensile permanent deformation within the above range; there are no particular restrictions on other physical properties or characteristics.

[0126] In this invention, the binder-forming polymer P1 preferably has an elongation at break of 100% or more. When the low-adsorption binder PB1 contains the binder-forming polymer P1 exhibiting an elongation at break of 100% or more, a strong adhesive force can be maintained even in the face of external stress, and consequently, the expansion and contraction of the constituent layer caused by charging and discharging, thereby further improving adhesion. From the viewpoint of maintaining dispersion stability, workability, and conductivity while further improving adhesion, the elongation at break of the binder-forming polymer P1 is preferably 200% or more, more preferably 400% or more, and even more preferably 600% or more. On the other hand, there is no particular upper limit to the elongation at break, which is practically 5000%, but from the viewpoint of maintaining dispersion stability and workability, it can be set to 3000% or less, preferably 2000% or less, and more preferably 1000% or less. The elongation at break is set as a value measured (calculated) by the method described in the examples.

[0127] In this invention, the elongation at break can be appropriately set according to the type of adhesive-forming polymer P1 (structure and composition of polymer chains) or the bonding mode of the main chain, the glass transition temperature, molecular weight distribution, stereoregularity, etc. of the adhesive-forming polymer P1.

[0128] The weight-average molecular weight of the binder-forming polymer P1 is not particularly limited, and is appropriately set considering the aforementioned tensile permanent deformation. The weight-average molecular weight of the binder-forming polymer is preferably 15,000 or more, more preferably 30,000 or more, and even more preferably 50,000 or more. As an upper limit, it is practically 5,000,000 or less, preferably 4,000,000 or less, more preferably 3,000,000 or less, even more preferably 1,000,000 or less, and particularly preferably 500,000 or less.

[0129] -Determination of molecular weight-

[0130] In this invention, the molecular weight of the polymer (polymer chain), unless otherwise specified, refers to the mass-average molecular weight converted from standard polystyrene obtained by gel permeation chromatography (GPC). As a method for its determination, methods under condition 1 or condition 2 (preferred) can be generally cited. Appropriate eluents are selected and used according to the type of polymer.

[0131] (Condition 1)

[0132] Column: Connects 2 TOSOH TSKgel Super AWM-H (trade name, manufactured by TOSOH CORPORATION)

[0133] Charge carriers: 10 mM LiBr / N-methylpyrrolidone

[0134] Measurement temperature: 40℃

[0135] Carrier flow rate: 1.0 ml / min

[0136] Sample concentration: 0.1% by mass

[0137] Detector: RI (Refractive Index) Detector

[0138] (Condition 2)

[0139] Tubes: Tubes connected to TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, and TOSOH TSKgel Super HZ2000 (all trade names, manufactured by Tosoh Corporation) are used.

[0140] Charge carrier: tetrahydrofuran

[0141] Measurement temperature: 40℃

[0142] Carrier flow rate: 1.0 ml / min

[0143] Sample concentration: 0.1% by mass

[0144] Detector: RI (Refractive Index) Detector

[0145] The binder-forming polymer P1 can be either a non-crosslinked polymer or a crosslinked polymer. Furthermore, when the polymer is crosslinked by heating or applying voltage, its molecular weight can be greater than the aforementioned molecular weight. Preferably, when starting to use an all-solid-state secondary battery, the mass-average molecular weight of the binder-forming polymer is within the aforementioned range.

[0146] The moisture concentration of the binder-forming polymer P1 (low-adsorption binder PB1) is preferably below 100 ppm (by mass). Furthermore, this low-adsorption polymer binder can be used to crystallize and dry the binder-forming polymer, or a dispersion of the binder-forming polymer can be used directly.

[0147] As long as the above-mentioned tensile permanent deformation is satisfied, there are no particular restrictions on the type and composition of the adhesive forming polymer P1. Considering the adsorption rate of the low-adsorption adhesive PB1, various polymers can be appropriately used as adhesive polymers for all-solid-state secondary batteries.

[0148] The binder forming polymer P1 is independent of the polymer type and has no particular restrictions on the bonding mode (arrangement) of the constituent components constituting its main chain. It can be any of random polymers, alternating polymers, block polymers, graft polymers, etc. From the viewpoint of easily exhibiting the tensile permanent deformation within the above range, block polymers are preferred.

[0149] In this invention, the polymer backbone refers to all linear molecular chains that constitute the polymer and can be considered branches or side groups relative to the backbone. While the molecular weight depends on the mass-average molecular weight of the branches considered as branches or side groups, typically the longest chain in the polymer's molecular chains becomes the backbone. However, terminal groups at the ends of the polymer are not included in the backbone. Furthermore, polymer side chains refer to branched chains other than the backbone, including both short and long chains. There are no particular limitations on the terminal groups of the polymer; suitable groups can be adopted through polymerization methods, etc. Examples include hydrogen atoms, alkyl groups, aryl groups, hydroxyl groups, and residues such as polymerization initiators.

[0150] There is no particular limitation on the number of blocks (chain segments) forming the block polymer, as long as it is 2 or more, and it can be set to 2 to 5, preferably 2 or 3.

[0151] When the different blocks forming the block polymer are designated as A, B, and C, examples of block polymers include AB type (a polymer in which one block A and one block B are bonded to form one polymer chain (main chain)), ABA type (a polymer in which two blocks A are bonded to both ends of one block B to form one polymer chain (main chain)), and ABC type (a polymer in which one block A, one block B, and one block C are sequentially bonded to form one polymer chain (main chain)). From the viewpoint of tensile permanent deformation, AB type or ABA type is preferred, and ABA type is more preferred.

[0152] In this invention, blocks A, B, and C can each be a block composed of one type of constituent element, or a block having two or more constituent elements. When there are two or more constituent elements, the bonding method (configuration) of each constituent element is not particularly limited, and can be any of random bonding, alternating bonding, block bonding, etc., with random bonding being preferred. The content of each constituent element in a block having two or more constituent elements is appropriately set, for example, based on the glass transition temperature preferably determined for each block.

[0153] In this invention, blocks A, B, and C can employ suitable blocks. For example, considering the glass transition temperature, block A is preferably a block exhibiting a higher glass transition temperature than block B, from the viewpoint of easily setting the tensile permanent deformation within the aforementioned range. Furthermore, considering the constituent components of the blocks, examples include blocks containing constituent components having specific functional groups, blocks containing constituent components derived from (meth)acrylate compounds (preferably compounds without specific functional groups), blocks containing constituent components derived from vinyl compounds (preferably compounds without specific functional groups), etc. From the viewpoint of improving the adhesion of solid particles, block A is preferably a block containing a component derived from a vinyl compound or (meth)acrylate compound without a specific functional group, or a block containing a component derived from a vinyl compound or (meth)acrylate compound with a glass transition temperature of 50°C or higher. More preferably, it is a block containing a component derived from a vinyl compound or (meth)acrylate compound without a specific functional group and with a glass transition temperature of 50°C or higher. Block B, from the viewpoint of improving the adhesion of solid particles, is preferably a block containing a component with a functional group or a block containing a component derived from a vinyl compound or (meth)acrylate compound (both preferably compounds without a specific functional group). More preferably, it is a block containing a component with a functional group or a block containing a component derived from a (meth)acrylate compound with a glass transition temperature of 15°C or lower. Even more preferably, it is a block containing both a component with a functional group and a component derived from a (meth)acrylate compound with a glass transition temperature of 15°C or lower. There are no particular restrictions on the combination of block A and block B, but from the perspective that the combination of the above-mentioned preferred blocks exhibits tensile permanent deformation within the above-mentioned range and has an excellent effect on improving the compactness of solid particles, it is preferred.

[0154] As block C, other blocks that do not correspond to blocks A and B can be cited. For example, blocks that contain constituents derived from compounds with a glass transition temperature of more than 15°C and less than 50°C, and do not contain constituents derived from vinyl compounds or (meth)acrylate compounds with a glass transition temperature of more than 50°C and constituents derived from (meth)acrylate compounds with a glass transition temperature of less than 15°C.

[0155] The glass transition temperature of block A is not particularly limited, but as mentioned above, it is preferably higher than that of block B. For example, from the viewpoint of tensile permanent deformation, it is preferably 30°C or higher, more preferably 50°C or higher, even more preferably 70°C or higher, and especially preferably 100°C or higher, and can also be set to 120°C or higher. The upper limit of the glass transition temperature is actually 300°C, for example, it can be set to 200°C, and preferably 150°C or lower. Furthermore, the mass-average molecular weight of block A is not particularly limited and can be appropriately set.

[0156] The glass transition temperature of block B is not particularly limited. For example, from the viewpoint of tensile permanent deformation, it can be set to 25°C or below, preferably 15°C or below, more preferably 0°C or below, further preferably -20°C or below, and especially preferably -40°C or below. The lower limit of the glass transition temperature is actually -150°C, for example, it can be set to -100°C, preferably -70°C or above. Furthermore, the mass-average molecular weight of block B is not particularly limited and can be appropriately set.

[0157] There is no particular limitation on the glass transition temperature of block C; it can be set to a temperature that is higher than but lower than the glass transition temperature of block A.

[0158] In this invention, the glass transition temperature of the above-mentioned compound and the glass transition temperature of the block have the same meaning as the glass transition temperature of the polymer composed of the compound or the polymer composed of the block, and are defined as the glass transition temperature measured by the following measurement method.

[0159] That is, the glass transition temperature of the compound is set as the glass transition temperature measured for a homopolymer composed of components derived from the compound. The glass transition temperature of a block is set as the corresponding glass transition temperature among the glass transition temperatures of block polymers containing that block. For example, the higher of two glass transition temperatures measured for an AB-type block polymer is set as the glass transition temperature of a block that is assumed to have a higher glass transition temperature. In addition, for cases where the glass transition temperature of a block in an AB-type block polymer cannot be measured (e.g., due to low peak intensity), the value is set as calculated by the following formula.

[0160] Formula: Tg S =(Tg C1 ×W C1 )+(Tg C2 ×W C2 )+……+(Tg Cn ×W Cn )

[0161] In the formula, Tg STg represents the glass transition temperature (°C) of the block. C1 Tg C2 ... Tg Cn W represents the glass transition temperature (°C) of each compound, C1, C2 to Cn, which constitutes the block. C1 W C2 ... W Cn This indicates the content (mass%) of each compound, which guides the formation of the block, C1, C2 to Cn, in the block.

[0162] The glass transition temperatures of the above homopolymers and block polymers were determined using dried samples of each polymer and a differential scanning calorimeter (DSC7000, manufactured by SII Crystal Technology Inc.) under the following conditions. The determination was performed twice on the same sample, and the result of the second determination was used.

[0163] • Measure the atmosphere in the chamber: nitrogen (50 mL / min)

[0164] • Heating rate: 5℃ / min

[0165] • Measurement start temperature: -100℃

[0166] • Measurement completion temperature: 200℃

[0167] • Sample tray: Aluminum tray

[0168] • Determine the mass of the sample: 5 mg

[0169] • Tg calculation: Tg is calculated by rounding the midpoint of the temperature between the starting and ending points of the DSC chart below the decimal point.

[0170] The glass transition temperature (Tg) of a block can be adjusted according to the composition of the block (the types and contents of the constituent components).

[0171] The end groups of block polymers are introduced with appropriate groups, such as hydrogen atoms, chain transfer agent residues, and initiator residues, through polymerization methods and polymerization stopping methods.

[0172] There are no particular restrictions on the synthesis methods of block polymers, and well-known methods can be used. For example, living radical polymerization can be cited. Examples of living radical polymerization methods include atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer polymerization (RAFT), and nitride-mediated polymerization (NMP).

[0173] As long as the adhesive forming polymer P1 exhibits the above-mentioned characteristics, its chemical structure, composition, etc. are not particularly limited, but it is preferred to have the following constituent components.

[0174] --Components containing functional groups--

[0175] The adhesive forming polymer P1 preferably comprises one or more constituent components having functional groups (including bonds) selected from the functional group (a) below, more preferably included in blocks A or B together with vinyl compounds or (meth)acrylate compounds (not having specific functional groups) described later. The constituent components having functional groups further enhance the adsorption and binding force of the low-adsorption adhesive PB1 to solid particles. Functional groups can be introduced into any constituent component forming the adhesive forming polymer. This constituent component only needs to have one (one type) functional group; typically, one to three functional groups are preferred.

[0176] Functional groups can be incorporated into the polymer backbone or into the side chains. When incorporated into the side chains, they form linkers that bond the functional groups to the backbone. There are no particular limitations on the type of linker; examples will be described later.

[0177] <Functional Groups (a)>

[0178] Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, ether (-O-), imino (=NR, -NR-), ester (-CO-O-), amide (-CO-NR-), carbamate (-NR-CO-O-), thiocarbamate (-NR-CS-O-, -NR-CO-S-, -NR-CS-S-), urea (-NR-CO-NR-), thiourea (-NR-CS-NR-), heterocyclic, aryl, carboxylic anhydride, fluoroalkyl, siloxane, carbonate (-O-CO-O-), ketone (-CO-)

[0179] The amino, sulfonyl, phosphate (phosphonyl), phosphonic acid, heterocyclic, and aryl groups included in functional group (a) are not particularly limited and have the same meaning as the corresponding groups of substituent Z described later. The amino group preferably has 0 to 12 carbon atoms, more preferably 0 to 6, and especially preferably 0 to 2. When amino, ether, imino (-NR-), ester, amide, carbamate, or urea bonds are included in a ring structure, it is classified as a heterocycle. Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, and thioalkyl groups that can obtain salts can form salts. Examples of salts include various metal salts, ammonium salts, or amine salts.

[0180] In the case of bonds such as ether bonds (-O-), the bonds enclosed in parentheses represent the bonds represented by chemical formulas within the parentheses. There are no particular limitations on the terminal groups bonded to these groups; groups selected from substituent Z described later can be cited, for example, alkyl groups. R in each bond represents a hydrogen atom or a substituent, preferably a hydrogen atom. There are no particular limitations on the substituents; they are selected from substituent Z described later, preferably alkyl groups. Furthermore, ether groups are included in carboxyl groups, hydroxyl groups, etc., but the -O- groups contained in these are not considered ether groups. The same applies to thioether groups. Also, regarding ketone bonds, carbonyl groups contained in ester bonds, etc., are not considered ketone bonds.

[0181] The carboxylic anhydride group is not particularly limited and includes groups formed by removing one or more hydrogen atoms from a dicarboxylic anhydride, components formed by copolymerization of polymeric dicarboxylic anhydrides, and ring-opening structures formed by the reaction of the aforementioned dicarboxylic anhydride with hydroxyl or amino groups such as water or alcohol. Groups formed by removing one or more hydrogen atoms from a dicarboxylic anhydride are preferably groups formed by removing one or more hydrogen atoms from a cyclic dicarboxylic anhydride. Examples of dicarboxylic anhydrides include acyclic dicarboxylic anhydrides such as acetic anhydride, propionic anhydride, and benzoic acid anhydride, and cyclic dicarboxylic anhydrides such as maleic anhydride, phthalic anhydride, fumaric acid anhydride, succinic anhydride, and itaconic anhydride. Polymeric dicarboxylic anhydrides are not particularly limited and include dicarboxylic anhydrides with intramolecular unsaturated bonds, but polymeric cyclic dicarboxylic anhydrides are preferred. Specifically, maleic anhydride and itaconic anhydride are examples. The carboxylic anhydride group derived from a cyclic dicarboxylic anhydride is also equivalent to a heterocyclic group, but is classified as a carboxylic anhydride group in this invention.

[0182] A fluoroalkyl group is an alkyl group or a group obtained by substituting at least one hydrogen atom in a cycloalkyl group with a fluorine atom, preferably having 1 to 20 carbon atoms, more preferably 2 to 15, and even more preferably 3 to 10. The number of fluorine atoms on the carbon atoms can be part of the substituted hydrogen atoms or all of them (perfluoroalkyl).

[0183] There are no particular limitations on the siloxane group; for example, it is preferred to have a siloxane group consisting of -(SiR2-O). n - indicates a structural group. R, as described above, is preferably alkyl or aryl. The repetition number n is preferably an integer from 1 to 100, more preferably an integer from 5 to 50, and even more preferably an integer from 10 to 30.

[0184] From the viewpoint of adsorption (adhesion) with solid particles and dispersion characteristics, the functional group is preferably a carboxyl group or a hydroxyl group, and more preferably a hydroxyl group.

[0185] In stepwise polymer polymerization, when the chemical structure of the polymer is represented by components derived from the starting material compounds, bonds such as ester bonds are broken down into -CO- groups and -O- groups, etc. Therefore, in this invention, the components having these bonds are designated as components derived from carboxylic acid compounds or isocyanate compounds, regardless of the polymer's labeling, and do not include components derived from polyols or polyamines.

[0186] Furthermore, in chain polymers, components with ester bonds (excluding ester bonds that form carboxyl groups) or aryl groups refer to components whose bonds are not directly bonded to the atoms constituting the main chain of the chain polymer. For example, they do not contain components derived from alkyl methacrylates or components derived from styrene compounds.

[0187] In the constituent components with functional groups, the portion of the structure incorporated into the main chain is not uniquely determined based on the type of polymer that forms the adhesive, as described later, and can be appropriately selected. For example, in the case of chain polymers, carbon-carbon bonds can be cited.

[0188] There are no particular limitations on the linking group used to connect the structure incorporated into the main chain and the aforementioned functional groups. Examples include alkylene groups (preferably 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3), alkenyl groups (preferably 2 to 6 carbon atoms, more preferably 2 to 3), aryl groups (preferably 6 to 24 carbon atoms, more preferably 6 to 10), oxygen atoms, sulfur atoms, and imino groups (-NR). N -:R N This refers to a group consisting of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. Other related groups include carbonyl groups, phosphate linkages (-OP(OH)(O)-O-), phosphonic acid linkages (-P(OH)(O)-O-), or combinations thereof. Preferably, the linkage is a group composed of an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom, and an imino group; more preferably, it is a group composed of a -CO-O- group or a -CO-N(R) group. N )-base(R N As described above, ) is a group formed by combining with alkylene or arylene groups.

[0189] In this invention, the number of atoms constituting the linking group is preferably 1 to 36, more preferably 1 to 24, even more preferably 1 to 12, and particularly preferably 1 to 6. The number of linking atoms in the linking group is preferably 12 or less, more preferably 10 or less, and particularly preferably 8 or less. A lower limit is 1 or more. The above-mentioned number of linking atoms refers to the minimum number of atoms connecting the defined structural parts. For example, in the case of -C(=O)-O-CH2-CH2-, the number of atoms constituting the linking group is 9, but the number of linking atoms is 4.

[0190] The portion of the main chain incorporated therein and the linker therein, in addition to the aforementioned functional groups, may or may not have substituents. Examples of possible substituents include groups selected from substituent Z other than the aforementioned functional groups.

[0191] There is no particular limitation on the glass transition temperature of the constituent components containing functional groups, but it is preferably below 15°C.

[0192] As constituent components having functional groups, preferred examples include compounds derived from (meth)acrylic acid compounds (M1), vinyl compounds (M2), etc., and dicarboxylic acid rods, which are described later as having functional groups introduced into the polymer. Furthermore, the method for introducing functional groups into the polymer will be described later.

[0193] --Components derived from (meth)acrylate compounds--

[0194] When the adhesive forming polymer P1 is a chain polymer described later, it is preferable to include one or more constituent components derived from (meth)acrylate compound (M1).

[0195] Examples of (meth)acrylate compounds (M1) include (meth)acrylate compounds, (meth)acrylamide compounds, and (meth)acrylonitrile compounds. Among these, (meth)acrylate compounds are preferred. Examples of (meth)acrylate compounds include (meth)acrylate alkyl ester compounds and (meth)acrylate aryl ester compounds, with (meth)acrylate alkyl ester compounds being the most preferred.

[0196] There is no particular limitation on the glass transition temperature of this component. When incorporated into the block polymer, it can be appropriately set according to each block, for example, set to above 50°C or below 15°C.

[0197] The alkyl group constituting the (meth)acrylate alkyl ester compound can be any of straight-chain, branched, or cyclic, and can be appropriately set considering factors such as the glass transition temperature of the constituent components. Furthermore, the number of carbon atoms in the alkyl group is not particularly limited, and can be set to, for example, 1 to 24, and can be appropriately set considering factors such as the glass transition temperature of the constituent components and the adhesion of the polymer binder to solid particles. For example, when the glass transition temperature of the constituent components is set to 50°C or higher, short-chain alkyl groups with 1 to 4 carbon atoms or cyclic alkyl groups with 3 to 20 carbon atoms (preferably 6 to 15) are preferred. On the other hand, when the glass transition temperature of the constituent components is set to 15°C or lower, alkyl groups with 1 to 20 carbon atoms are preferred, and long-chain alkyl groups are more preferred. The number of carbon atoms in long-chain alkyl groups is more preferably 4 to 16, and even more preferably 6 to 14. The number of carbon atoms in the aryl group constituting the aryl ester is not particularly limited, and can be set to, for example, 6 to 24, more preferably 6 to 10, and preferably 6. In (meth)acrylamide compounds, the nitrogen atom of the amide group can be replaced by an alkyl or aryl group.

[0198] The (meth)acrylic acid compound (M1) preferably does not have the above-mentioned functional groups.

[0199] (Components derived from (meth)acrylate compounds with a glass transition temperature above 50°C)

[0200] The (meth)acrylate compound with a glass transition temperature of 50°C or higher is preferably a constituent derived from the (meth)acrylate compound (M1) described above, which has a glass transition temperature of 50°C or higher. From the viewpoint of tensile permanent deformation, the glass transition temperature of the (meth)acrylate compound from which this constituent is derived is preferably 80°C or higher, more preferably 100°C or higher, even more preferably 110°C or higher, and particularly preferably 130°C or higher. The upper limit of the glass transition temperature is practically 300°C, but for example, it can be set to 200°C.

[0201] Examples of compounds with a glass transition temperature above 50°C include short-chain alkyl esters of (meth)acrylates such as methyl methacrylate, ethyl methacrylate, benzyl methacrylate, and tert-butyl methacrylate; cyclic alkyl esters of (meth)acrylates such as cyclohexyl methacrylate, isobornyl methacrylate, adamantane methacrylate, dicyclopentyl methacrylate, dicyclopentenyl methacrylate, and dicyclopentenoxyethyl methacrylate. Furthermore, examples include (meth)acrylamide compounds such as (meth)acrylamide, N-isopropyl(meth)acrylamide, dimethyl(meth)acrylamide, and tert-butyl(meth)acrylamide; phenyl (meth)acrylate; and (meth)acrylonitrile compounds.

[0202] (Components derived from (meth)acrylate compounds with a glass transition temperature below 15°C)

[0203] The (meth)acrylate compound with a glass transition temperature of 15°C or less is preferably a constituent derived from the (meth)acrylate compound (M1) described above, which has a glass transition temperature of 15°C or less. From the viewpoint of tensile permanent deformation, the glass transition temperature of the (meth)acrylate compound from which this constituent is derived is preferably 0°C or less, more preferably -15°C or less, and even more preferably -30°C or less. The lower limit of the glass transition temperature is practically -150°C, but can be set to, for example, -100°C.

[0204] Examples of compounds with a glass transition temperature below 15°C include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, octyl acrylate, ethylhexyl acrylate, decyl acrylate, dodecyl acrylate, and tetradecyl acrylate. Examples of hydroxyalkyl acrylate compounds include hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxybutyl acrylate, as well as 2-methacryloyloxyethyl succinic acid. Furthermore, examples of polyethylene glycol methacrylate, polypropylene glycol methacrylate, and polyalkylene glycol methacrylate methacrylates are also included.

[0205] --Components derived from vinyl compounds--

[0206] When the adhesive forming polymer P1 is a chain polymer as described later, it is also a preferred method to include one or more constituent components derived from vinyl compounds (M2).

[0207] There are no particular limitations on what constitutes a vinyl compound (M2), and examples include aromatic vinyl compounds such as styrene compounds, vinylnaphthalene compounds, vinylcarbazole compounds, vinylimidazol compounds, and vinylpyridine compounds, as well as allyl compounds, vinyl ether compounds, and vinyl ester compounds (e.g., vinyl acetate compounds). Examples of vinyl compounds include "ethylene monomers" as described in Japanese Patent Application Publication No. 2015-88486.

[0208] There is no particular limitation on the glass transition temperature of this component. When incorporated into the block polymer, it can be appropriately set according to each block, for example, set to above 50°C or below 15°C.

[0209] Examples of vinyl compounds with a glass transition temperature of 50°C or higher include styrene compounds, vinylnaphthalene compounds, vinylcarbazole compounds, vinylpyridine compounds, vinylimidazole compounds, and N-vinylcaprolactam. On the other hand, examples of vinyl compounds with a glass transition temperature of 15°C or lower include vinyl acetate and vinyl ether compounds.

[0210] (Meth)acrylic acid compounds and vinyl compounds may each have substituents. There are no particular limitations on the substituents, and groups selected from substituent Z described later can be cited.

[0211] The adhesive forming polymer may have one or more of the above-mentioned components.

[0212] As an adhesive forming polymer P1 exhibiting the above-mentioned range of tensile permanent deformation, a polymer having a polymeric chain having at least one type of bond selected from urethane bonds, urea bonds, amide bonds, imide bonds, ester bonds, ether bonds and carbonate bonds, or carbon-carbon double bonds on the main chain is preferably exemplified.

[0213] The aforementioned bonds are not particularly limited as long as they are included in the polymer backbone. They can be any form contained in the constituent components (repeating units) and / or contained as bonds connecting different constituent components to each other. Furthermore, the bonds contained in the backbone are not limited to one type; they can be two or more types, preferably one to six types, and more preferably one to four types. In this case, the bonding mode of the backbone is not particularly limited; it can randomly have two or more types of bonds, or it can be a partitioned backbone with partitions of specific bonds and partitions of other bonds.

[0214] Polymers that have urethane bonds, urea bonds, amide bonds, imide bonds, ester bonds, ether bonds, and carbonate bonds in their main chain, as mentioned above, include, for example, stepwise polymers (condensation, addition, or addition condensation) such as polyurethane, polyurea, polyamide, polyimide, polyester, polyether, and polycarbonate, or copolymers thereof. The copolymer can be a block copolymer in which the above polymers are used as chain segments, or a random copolymer formed by the random bonding of the constituent components of two or more of the above polymers.

[0215] Examples of chain polymers having carbon-carbon double bonds in their main chain include fluoropolymers, hydrocarbon polymers, vinyl polymers, and (meth)acrylic acid polymers. There are no particular limitations on the polymerization method of these chain polymers; they can be any of block copolymers, alternating copolymers, or random copolymers. From the viewpoint of exhibiting the tensile permanent deformation range described above, block copolymers are preferred.

[0216] As the binder forming polymer P1, the above-mentioned polymers can be appropriately selected, but polymers with carbon-carbon double bonds in the main chain are preferred, and chain polymers are more preferred. From the viewpoint of maintaining dispersion stability and operability while further improving resistance and cycling characteristics, (meth)acrylic acid polymers, fluoropolymers or vinyl polymers are preferred, and (meth)acrylic acid polymers are more preferred.

[0217] Regarding the preferred (meth)acrylic polymer for forming polymer P1 as an adhesive, examples include copolymers containing components derived from (meth)acrylic acid compound (M1), preferably containing components having functional groups, and polymers composed of copolymers containing 50% by mass or more of components derived from (meth)acrylic acid compound. Here, when the components having functional groups are (meth)acrylic acid compounds or components derived from (meth)acrylic acid compounds, the content of the components having functional groups is included in the content of components derived from (meth)acrylic acid compound. As a (meth)acrylic polymer, copolymers further containing components derived from vinyl compounds are also preferred. In this case, the content of components derived from vinyl compounds in the polymer is 50% by mass or less, preferably 3 to 40% by mass, more preferably 3 to 30% by mass.

[0218] Regarding the vinyl polymer preferred as the binder forming polymer P1, examples include copolymers containing components derived from vinyl compounds (M2), preferably components having functional groups, and polymers composed of copolymers containing 50% by mass or more of components derived from vinyl compounds. Here, when the components having functional groups are derived from vinyl compounds, the content of the components having functional groups is included in the content of components derived from vinyl compounds. Furthermore, copolymers containing components derived from (meth)acrylic acid compounds are also preferred as vinyl polymers. In this case, the content of the polymer containing components derived from (meth)acrylic acid compounds is less than 50% by mass, for example, preferably 0 to 40% by mass, more preferably 0 to 30% by mass.

[0219] Preferred fluoropolymers for forming polymer P1 as adhesives include (co)polymers of polymeric compounds containing fluorine atoms (fluorinated polymeric compounds). Further preferred fluoropolymers are copolymers comprising components having functional groups, components derived from (meth)acrylic acid compounds, components derived from vinyl compounds, etc.

[0220] There are no particular limitations on the fluorinated polymerizable compounds, and examples include compounds commonly used in fluorinated polymers. For example, this refers to compounds in which fluorine atoms are directly or via a linker group bonded to a carbon-carbon double bond. There are no particular limitations on the linker group, and examples include linkers in constituent components having the aforementioned functional groups. Examples of fluorinated polymerizable compounds include fluorinated vinylidene fluoride (VDF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), trifluoroethylene, monofluoroethylene, trifluorochloroethylene, and perfluoroalkyl ethers such as trifluoromethyl vinyl ether and pentafluoroethyl vinyl ether.

[0221] Examples of fluoropolymers include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), copolymers of PVdF and hexafluoropropylene (PVdF-HFP), and copolymers of PVdF, hexafluoropropylene, and tetrafluoroethylene (PVdF-HFP-TFE). The content of each component in the fluoropolymer can be appropriately determined considering factors such as glass transition temperature and tensile permanent deformation. For example, in PVdF-HFP, the copolymerization ratio of PVdF to HFP [PVdF:HFP] (mass ratio) is not particularly limited, but is preferably 9:1 to 5:5. In PVdF-HFP-TFE, the copolymerization ratio of PVdF, HFP, and TFE [PVdF:HFP:TFE] (mass ratio) is not particularly limited, but is preferably 20 to 60:10 to 40:5 to 30.

[0222] Regarding the preferred hydrocarbon polymers for forming polymer P1 as an adhesive, examples include polyethylene, polypropylene, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene-butadiene copolymers, styrene-based thermoplastic elastomers, polybutene, acrylonitrile-butadiene copolymers, or their hydrogenated polymers. There are no particular limitations on styrene-based thermoplastic elastomers or their hydrogenated forms; examples include styrene-ethylene-butene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), hydrogenated SIS, styrene-butadiene-styrene block copolymers (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers of SEBS and the aforementioned block copolymers. In this invention, the preferred feature of the hydrocarbon polymer is that the polymer without unsaturated groups (e.g., 1,2-butadiene components) bonded to the main chain can suppress the formation of chemical crosslinks.

[0223] As (meth)acrylic acid compound (M1) and vinyl compound (M2), compounds represented by the following formula (b-1) are preferred. When the compound has a functional group selected from the functional group (a) above, it is equivalent to deriving a compound having the constituent components of the above functional group.

[0224] [Chemical Formula 1]

[0225]

[0226] In the formula, R 1 The group represents a hydrogen atom, hydroxyl group, cyano group, halogen atom, alkyl group (preferably with 1 to 24 carbon atoms, more preferably 1 to 12, especially preferably 1 to 6), alkenyl group (preferably with 2 to 24 carbon atoms, more preferably 2 to 12, especially preferably 2 to 6), alkynyl group (preferably with 2 to 24 carbon atoms, more preferably 2 to 12, especially preferably 2 to 6), or aryl group (preferably with 6 to 22 carbon atoms, more preferably 6 to 14). Among these, hydrogen atoms or alkyl groups are preferred, and hydrogen atoms or methyl groups are even more preferred.

[0227] R 2 Represents a hydrogen atom or substituent. It can be represented as R. 2 The substituents are not particularly limited, and examples include alkyl (which may be branched, but preferably straight-chain), alkenyl (preferably with 2 to 12 carbon atoms, more preferably 2 to 6, especially preferably 2 or 3), aryl (preferably with 6 to 22 carbon atoms, more preferably 6 to 14), aralkyl (preferably with 7 to 23 carbon atoms, more preferably 7 to 15), and cyano. The number of carbon atoms of the alkyl group has the same meaning as the number of carbon atoms of the alkyl group constituting the above-mentioned alkyl methacrylate compound, and the preferred range is also the same.

[0228] L 1 The term "linking group" is not particularly limited; examples of linking groups among the aforementioned constituents containing functional groups can be cited. Among them, L... 1 Especially preferred is the -CO-O- group.

[0229] n is 0 or 1, preferably 1. Where, -(L 1 ) n -R 2 In the case of a substituent (e.g., alkyl), set n to 0 and R to 0. 2 Set as a substituent (alkyl).

[0230] In the above formula (b-1), the carbon atom that forms the polymerizable group and is not bonded to R 1 The carbon atom is represented as an unsubstituted carbon atom (H₂C=), but it can have substituents. There are no particular restrictions on the substituents, but for example, R can be used. 1 The above-mentioned groups.

[0231] Furthermore, substituents such as alkyl, aryl, alkylene, and aryl groups may be included without impairing the effects of the present invention. There are no particular limitations on the substituents; for example, groups selected from substituent Z described later can be cited, specifically, halogen atoms, etc.

[0232] The content of each component in the adhesive-forming polymer P1 is not particularly limited, and can be determined by taking into account the tensile permanent deformation, adsorption rate, etc. of the polymer, for example, by setting it to the following range.

[0233] The content of each component in the adhesive forming polymer P1 is set within the following range, for example, so that the total content of all components is 100% by mass. Furthermore, when there are two or more components that correspond to a specific component, the content of the specific component is set to the total content of the two or more components.

[0234] The content of the functional group-containing component in the binder-forming polymer P1 is not particularly limited as long as it can suppress the adsorption rate of the low-adsorption binder PB1 to the inorganic solid electrolyte to less than 60%. For example, from the viewpoint of improving the dispersion characteristics of solid particles while setting the tensile permanent deformation within the above-mentioned range, it is preferably 0.1 to 50% by mass, more preferably 0.1 to 20% by mass, even more preferably 0.5 to 20% by mass, and particularly preferably 1 to 10% by mass. Among these, the content of the component containing carboxyl groups is preferably less than 10% by mass, more preferably 0.1 to 5% by mass, and even more preferably 0.2 to 3% by mass.

[0235] The functional group of the constituent is preferably contained in the chain segment containing the constituent derived from the (meth)acrylate compound with a glass transition temperature of 15°C or less, and the content of the constituent is also set within the above range.

[0236] The total content of components derived from (meth)acrylic acid compounds in the binder-forming polymer P1 is not particularly limited and can be appropriately determined. For example, when the binder-forming polymer P1 is a (meth)acrylic acid polymer, it is 50% by mass or more, preferably 50 to 100% by mass, more preferably 65 to 100% by mass, and even more preferably 80 to 100% by mass.

[0237] The content of components derived from (meth)acrylic acid compounds in the binder-forming polymer P1 is not particularly limited, and can be appropriately determined considering the total content mentioned above. For example, when the binder-forming polymer P1 is a (meth)acrylic acid polymer, it is 30% by mass or more, preferably 40 to 100% by mass, more preferably 60 to 100% by mass, and even more preferably 75 to 100% by mass.

[0238] The content of components derived from (meth)acrylate compounds with a glass transition temperature of 50°C or higher in the binder-forming polymer P1 is not particularly limited, and can be appropriately determined considering factors such as tensile permanent deformation, adsorption rate, and the total content of the aforementioned components derived from (meth)acrylate compounds. For example, when the binder-forming polymer P1 is a (meth)acrylate polymer, it is preferably 3 to 50% by mass, more preferably 5 to 40% by mass, and even more preferably 10 to 30% by mass. When the binder-forming polymer P1 is another chain polymer, it is preferably 0 to 50% by mass, more preferably 10 to 30% by mass. In the chain segment containing components derived from vinyl compounds or (meth)acrylate compounds with a glass transition temperature of 50°C or higher, the content of components derived from (meth)acrylate compounds with a glass transition temperature of 50°C or higher can be appropriately set considering the content in the aforementioned binder-forming polymer P1. For example, it can be set to 0 to 100% by mass among all components constituting the chain segment, preferably 50 to 100% by mass.

[0239] Furthermore, the content of the constituent components derived from (meth)acrylate compounds with a glass transition temperature of 15°C or lower in the binder-forming polymer P1 is not particularly limited, and can be appropriately determined considering factors such as tensile permanent deformation, adsorption rate, and the total content of the constituent components derived from (meth)acrylate compounds. For example, when the binder-forming polymer P1 is a (meth)acrylate polymer, it is preferably 50 to 97% by mass, more preferably 60 to 95% by mass, and even more preferably 70 to 90% by mass. When the binder-forming polymer P1 is another chain polymer, it is preferably 50 to 100% by mass, more preferably 70 to 90% by mass. In the chain segment containing the constituent components derived from (meth)acrylate compounds with a glass transition temperature of 15°C or lower, the content of the constituent components derived from (meth)acrylate compounds with a glass transition temperature of 15°C or lower can be appropriately set considering the content in the binder-forming polymer P1. For example, it can be set to 0 to 100% by mass among all the constituent components constituting the chain segment, preferably 50 to 100% by mass.

[0240] The total content of components derived from vinyl compounds in the binder-forming polymer P1 is not particularly limited and can be appropriately determined. For example, when the binder-forming polymer P1 is a vinyl polymer, it is 50% by mass or more, preferably 50 to 100% by mass, more preferably 60 to 100% by mass, and even more preferably 75 to 100% by mass. When the binder-forming polymer P1 is another type of chain polymer, it is less than 50% by mass.

[0241] The content of components derived from vinyl compounds with a glass transition temperature of 50°C or higher in the binder-forming polymer P1 is not particularly limited, and can be appropriately determined by considering factors such as tensile permanent deformation, adsorption rate, and the total content of the aforementioned components derived from vinyl compounds. For example, when the binder-forming polymer P1 is a vinyl polymer or a hydrocarbon polymer, it is preferably 5 to 40% by mass, more preferably 10 to 30% by mass, and even more preferably 15 to 20% by mass. When the binder-forming polymer P1 is another chain polymer, it is preferably 0 to 50% by mass, more preferably 10 to 30% by mass.

[0242] When the binder forming polymer P1 is a block polymer, there is no particular limitation on the content of each block in the binder forming polymer, and it can be appropriately determined by taking into account tensile permanent deformation, adsorption rate, and the above (total) content.

[0243] From the viewpoint of tensile permanent deformation and adsorption rate, the content of segments with high glass transition temperatures, such as segments A comprising vinyl compounds or (meth)acrylate compounds with glass transition temperatures of 50°C or higher, in the binder-forming polymer is preferably 3 to 50% by mass, more preferably 5 to 40% by mass, and even more preferably 10 to 30% by mass. When the block polymer contains two or more segments A (e.g., ABA-type block polymers), the content of the aforementioned segment A is set as the total content of the two or more segments A. In this case, the content ratio of the two segments A can be appropriately set, for example, it can be set to 1:5 to 5:1 (mass ratio).

[0244] On the other hand, from the viewpoint of tensile permanent deformation and adsorption rate, the content of blocks with low glass transition temperatures, such as segments B comprising components derived from (meth)acrylate compounds with glass transition temperatures below 15°C, in the binder-forming polymer is preferably 50–97% by mass, more preferably 60–95% by mass, and even more preferably 70–90% by mass. When the above-mentioned content of segment B also includes two or more segments B, it is defined as the total content. In this case, the content ratio of the two segments B can be appropriately set, and can be set within the same range as the content ratio of the two segments A mentioned above.

[0245] When the block polymer has other blocks that do not correspond to either block A or block B, such as block C mentioned above, there is no particular limitation on the content of such block in the adhesive forming polymer, for example, it can be set to less than 30% by mass.

[0246] The adhesive forming polymer P1 may have substituents. There are no particular limitations on the substituents, but groups selected from the substituents Z below are preferred.

[0247] The binder forming polymer P1 is synthesized by selecting the raw material compound according to the type of bonds in the main chain and by using known methods, and by subjecting the raw material compound to polyaddition, condensation, or chain polymerization.

[0248] -Substituent Z-

[0249] Examples of alkyl groups include alkyl groups (preferably alkyl groups with 1 to 20 carbon atoms, such as methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably alkenyl groups with 2 to 20 carbon atoms, such as vinyl, allyl, oleyl, etc.), alkynyl groups (preferably alkynyl groups with 2 to 20 carbon atoms, such as ethynyl, butyrynyl, phenylethynyl, etc.), and cycloalkyl groups (preferably cycloalkyl groups with 3 to 20 carbon atoms, such as cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc.). When the alkyl group is used in this specification... Generally, this indicates the presence of cycloalkyl groups, but they are described separately here. These groups include aryl groups (preferably aryl groups with 6 to 26 carbon atoms, such as phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl groups (preferably aralkyl groups with 7 to 23 carbon atoms, such as benzyl, phenethyl, etc.), and heterocyclic groups (preferably heterocyclic groups with 2 to 20 carbon atoms, more preferably heterocyclic groups having at least one oxygen, sulfur, and nitrogen atom in a 5- or 6-membered ring). Heterocyclic groups include aromatic heterocyclic groups and aliphatic heterocyclic groups. Examples include tetrahydropyranyl, tetrahydrofuranyl, and 2-pyridyl. 4-pyridinyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidone, etc.), alkoxy groups (preferably alkoxy groups with 1 to 20 carbon atoms, such as methoxy, ethoxy, isopropoxy, benzyloxy, etc.), aryloxy groups (preferably aryloxy groups with 6 to 26 carbon atoms, such as phenoxy, 1-naphthoxy, 3-methylphenoxy, 4-methoxyphenoxy, etc.), heterocyclic oxy groups (groups with -O- groups bonded to the above heterocyclic groups), alkoxycarbonyl groups (preferably alkoxycarbonyl groups with 2 to 20 carbon atoms, such as ethoxycarbonyl, 2-ethylhexyloxycarbonyl, etc.). Dodecyloxycarbonyl, etc.), aryloxycarbonyl (preferably aryloxycarbonyl with 6 to 26 carbon atoms, such as phenoxycarbonyl, 1-naphthoxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), heterocyclic oxycarbonyl (a group with -O-CO- group bonded to the above heterocyclic group), amino (preferably containing amino, alkylamino, arylamino with 0 to 20 carbon atoms, such as amino(-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, aniline, etc.), aminosulfonyl (preferably aminosulfonyl with 0 to 20 carbon atoms, such as N,N-dimethylaminosulfonyl, N-phenylaminosulfonyl, etc.), acyl groups (including alkyl carbonyl, alkenyl carbonyl, alkynyl carbonyl, aryl carbonyl, heterocyclic carbonyl, preferably acyl groups with 1 to 20 carbon atoms, such as acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryl, methacryl, crotonyl, benzoyl, naphthoyl, nicotinyl, etc.), acyloxy groups (including alkyl carbonyloxy, alkenyl carbonyloxy, alkynyl carbonyloxy, heterocyclic carbonyloxy, preferably acyloxy groups with 1 to 20 carbon atoms, such as acetyloxy, propionyloxy, butyryloxy, octanoyloxy, hexadecanoyl, etc.), Acryloyloxy, methacryloyloxy, crotonyloxy, nicotinoxy, etc.), aromatic acryloyloxy (preferably aromatic acryloyloxy with 7 to 23 carbon atoms, such as benzoyloxy, naphthyloxy, etc.), carbamoyl (preferably carbamoyl with 1 to 20 carbon atoms, such as N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), amide (preferably amide with 1 to 20 carbon atoms, such as acetamido, benzoylamino, etc.), alkylthio (preferably alkylthio with 1 to 20 carbon atoms, such as methylthio, ethylthio, isopropylthio, benzylthio, etc.) Arylthioyl (preferably arylthioyl with 6 to 26 carbon atoms, such as phenylthioyl, 1-naphthioyl, 3-methylphenylthioyl, 4-methoxyphenylthioyl, etc.), heterocyclic thioyl (a group with -S- group bonded to the above heterocyclic group), alkylsulfonyl (preferably alkylsulfonyl with 1 to 20 carbon atoms, such as methylsulfonyl, ethylsulfonyl, etc.), arylsulfonyl (preferably arylsulfonyl with 6 to 22 carbon atoms, such as benzenesulfonyl, etc.), alkylsilyl (preferably alkylsilyl with 1 to 20 carbon atoms, such as monomethylsilyl, dimethylsilyl, trimethylsilyl, etc.). alkylsilyl, triethylsilyl, etc.), arylsilyl (preferably arylsilyl with 6 to 42 carbon atoms, such as triphenylsilyl), alkoxysilyl (preferably alkoxysilyl with 1 to 20 carbon atoms, such as monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl (preferably aryloxysilyl with 6 to 42 carbon atoms, such as triphenoxysilyl), phosphoryl (preferably phosphoric acid with 0 to 20 carbon atoms, such as -OP(=O)(R, P )2) Phosphonyl group (preferably a phosphonyl group with 0 to 20 carbon atoms, for example, -P(=O)(R P )2) Oxyphosphin group (preferably oxyphosphin group with 0 to 20 carbon atoms, for example, -P(R P 2) Phosphonic acid group (preferably a phosphonic acid group with 0 to 20 carbon atoms, for example, -PO(OR) P 2) Sulfonate (sulfonic acid group), carboxyl group, hydroxyl group, thioalkyl group, cyano group, halogen atom (e.g., fluorine atom, chlorine atom, bromine atom, iodine atom, etc.). R PIt is a hydrogen atom or a substituent (preferably a group selected from substituent Z).

[0250] Furthermore, each of the groups listed in these substituents Z can be further replaced by the aforementioned substituents Z.

[0251] The aforementioned alkyl, alkylene, alkenyl, alkenylene, ynyl and / or ynylene groups can be cyclic or chain-like, and can be straight-chain or branched.

[0252] As a specific example of the adhesive forming polymer P1, there are other polymers synthesized in the examples, but the invention is not limited to these.

[0253] The polymer binder may contain one or more binder-forming polymers. Furthermore, the polymer binder may contain other polymers, provided that the function of the binder-forming polymer is not impaired. Among these other polymers, polymers commonly used as binders in all-solid-state secondary batteries can be used without particular restriction.

[0254] The total content of the binder PB in the inorganic solid electrolyte composition is not particularly limited, but from the viewpoint of dispersion stability and operability, as well as resistance reduction and cycling characteristics, it is preferably 0.1 to 10.0% by mass, more preferably 0.2 to 5.0% by mass, and even more preferably 0.3 to 4.0% by mass. On the other hand, for the same reason, the solid content in 100% by mass is preferably 0.1 to 10.0% by mass, more preferably 0.3 to 8% by mass, and even more preferably 0.5 to 7% by mass.

[0255] In this invention, the mass ratio of the total mass (total amount) of the inorganic solid electrolyte and the active material to the total mass of the polymer binder PB in 100% by mass of the solid component [(mass of inorganic solid electrolyte + mass of active material) / (total mass of polymer binder PB)] is preferably in the range of 1,000 to 1. Furthermore, this ratio is more preferably 500 to 2, and even more preferably 100 to 10.

[0256] When the inorganic solid electrolyte composition contains a binder other than the low-adsorption binder PB1, the content (solid content) of the low-adsorption binder PB1 can be higher than, but preferably the same as or lower than, the total content (solid content) of the binders other than the low-adsorption binder PB1. Therefore, in the case of binders other than the low-adsorption binder PB1, particularly particulate binder PB2, excellent dispersion stability and workability can be maintained, and adhesion can be further enhanced. On the other hand, when the binder other than the low-adsorption binder PB1 includes a polymer binder PB3 composed of a chain polymer (excluding the polymer with a tensile permanent deformation of less than 50%), adhesion can be maintained while dispersion stability, ionic conductivity, and cycling characteristics are further enhanced. The difference (absolute value) between the content of the low-adsorption binder PB1 and the total content of the binders other than the low-adsorption binder is not particularly limited; for example, it can be set to 0-8% by mass, more preferably 0-4% by mass, and even more preferably 0-2% by mass. Furthermore, the ratio of the content of the low-adsorption adhesive PB1 to the content of other adhesives (content of low-adsorption adhesive / total content of other adhesives) is not particularly limited. For example, it is preferably 0.01 to 10, more preferably 0.02 to 5, further preferably 0.03 to 2.0, especially preferably 0.04 to 1.0, and most preferably 0.05 to 0.2.

[0257] When the adhesive, other than the low-adsorption adhesive, contains multiple types of adhesives, such as polymer adhesives containing polymers with tensile permanent deformation that is unmeasurable or more than 50%, high-adsorption adhesives, particulate adhesives PB2, and polymer adhesives PB3 composed of chain polymers, the content of each adhesive type, the difference (absolute value) between the content of the low-adsorption adhesive and the content of the low-adsorption adhesive, and the ratio to the content of the low-adsorption adhesive PB1 can be appropriately determined, for example, set to the above-mentioned ranges for adhesives other than the low-adsorption adhesive. The content ratio of the low-adsorption adhesive PB1 to the particulate adhesive PB2 (content of low-adsorption adhesive PB1 / content of particulate adhesive PB2) is preferably 0.01 to 10, more preferably 0.02 to 5, and even more preferably 0.05 to 3.0.

[0258] (Particle-shaped adhesive PB2)

[0259] In addition to the aforementioned low-adsorption binder PB1, the composition containing inorganic solid electrolyte of the present invention preferably contains one or more particulate polymer binders (particulate binders) PB2 that are insoluble in the composition. The shape of the particulate binder is not particularly limited and can be flat, amorphous, etc., but is preferably spherical or granular. The average particle size of the particulate binder is preferably 1–1000 nm, more preferably 10–800 nm, further preferably 20–500 nm, and particularly preferably 40–300 nm. The average particle size can be measured in the same manner as the particle size of the aforementioned inorganic solid electrolyte.

[0260] The granular binder PB2 is preferably a granular binder with an adsorption rate of 60% or more for inorganic solid electrolytes. The adsorption rate for active substances can be appropriately determined. The polymer P2 forming the granular binder can be appropriately selected from the above-mentioned step-polymerization polymers, the above-mentioned chain-polymerization polymers, etc., and is preferably a random polymer. There are no particular limitations on the tensile permanent deformation of the polymer, but it is preferably unmeasurable or 50% or more.

[0261] If the inorganic solid electrolyte composition contains particulate binder PB2, the improved dispersion stability and operability of the binder-based polymer P1 are not compromised, and the adhesion of solid particles is enhanced while suppressing the increase in interfacial resistance. As a result, cycle characteristics can be further improved for all-solid-state secondary batteries, and preferably, further reduction in resistance can be achieved.

[0262] As the particulate binder PB2, various particulate binders used in the manufacture of all-solid-state secondary batteries can be used without particular limitation. For example, particulate binders composed of step-polymerized polymers or chain-polymerized polymers can be cited; specifically, polymer Lx-1 synthesized in the examples can be cited. Furthermore, binders described in Japanese Patent Application Publication No. 2015-088486, International Publication No. 2018 / 020827, etc., can also be cited.

[0263] There are no particular limitations on step-polymers, and examples include polyurethanes, polyureas, polyamides, polyimides, polyesters, and polycarbonates. There are also no particular limitations on chain polymers, and examples include fluoropolymers (also known as fluorinated copolymers), hydrocarbon polymers, vinyl polymers, and (meth)acrylic polymers (polymers described later).

[0264] There is no particular limitation on the content of the particulate binder in the composition containing inorganic solid electrolytes. From the viewpoint of improving dispersion stability and workability, and thus exhibiting adhesion, it is preferable to have 0.02 to 5.0% by mass of the solid component per 100% by mass, more preferably 0.05 to 3.0% by mass, and even more preferably 0.1 to 2.0% by mass. In addition, the content of the particulate binder can be appropriately set within the above range, but considering the solubility of the particulate binder, it is preferable to have a content that is insoluble in the composition containing inorganic solid electrolytes.

[0265] (PB3, a polymer adhesive composed of chain polymers)

[0266] The inorganic solid electrolyte composition of the present invention, as a polymer binder PB, preferably contains one or more polymer binders (sometimes referred to as chain polymer binders) PB3 composed of chain polymers, in addition to the aforementioned low-adsorption binder PB1. If the inorganic solid electrolyte composition contains chain polymer binder PB3, dispersion stability and operability can be further improved without compromising adhesion, and cycling characteristics and ionic conductivity can be further improved.

[0267] The chain polymer binder PB3 may be insoluble in the dispersion medium of the composition, but is preferably soluble. Furthermore, the chain polymer binder preferably has an adsorption rate of less than 60% for inorganic solid electrolytes, a preferred range being the same as that of the binder-formed polymer with a tensile permanent deformation of less than 50%. The adsorption rate for active substances can be appropriately determined. Each adsorption rate can be measured using the methods described above.

[0268] The chain polymer P3 used to form the chain polymer binder PB3 is not particularly limited, and hydrocarbon polymers, vinyl polymers, and (meth)acrylic polymers are preferred examples. The polymerization method of these chain polymers is not particularly limited, and they can be any of block copolymers, alternating copolymers, or random copolymers, with random copolymers being preferred. The tensile permanent deformation of the chain polymer is not particularly limited, but is preferably unmeasurable or 50% or more.

[0269] The chain polymer P3 may contain, for example, a constituent having functional groups selected from the group (a) of functional groups described in the above-described adhesive-forming polymers with a tensile permanent deformation of less than 50% as substituents (a constituent having functional groups). The constituent having functional groups has the function of improving the adsorption rate of the chain polymer adhesive PB3 for inorganic solid electrolytes, and may be any constituent forming the chain polymer P3. Functional groups may be incorporated into the main chain of the chain polymer or into the side chains. When incorporated into the side chains, a linker is provided that bonds the functional groups to the main chain. There are no particular limitations on the linker; examples include linkers that connect the structure incorporated into the main chain to the aforementioned functional groups. A constituent may have one or more functional groups, and when it has two or more, they may or may not be bonded to each other.

[0270] A constituent having ester bonds (excluding ester bonds that form carboxyl groups) or amide bonds as functional groups refers to a constituent whose ester bonds or amide bonds are not directly bonded to the atoms that make up the main chain, for example, a constituent that does not contain constituents derived from alkyl methacrylates.

[0271] The content (molar basis) of the constituent components having the above-mentioned functional groups in polymer P3 is not particularly limited, but from the viewpoint of the adhesiveness of solid particles, it is preferably 0.01 to 70 mol%, more preferably 1 to 20 mol%, and even more preferably 3 to 10 mol%. The content (mass basis) of the constituent components having functional groups is not particularly limited, but for the same reasons as above, it is within the same range as the content of the constituent components having functional groups in the adhesive-forming polymer P1. A particularly preferred range is 0.5 to 5% by mass.

[0272] As a method for introducing functional groups, examples include copolymerization of a compound containing a functional group (a) with a polymer chain during polymerization. Other methods include polymerization with an initiator or chain transfer agent containing a functional group to introduce functional groups at the polymer terminus, and polymerization of functional groups at the side chains or terminus through polymer reactions. Commercially available chain polymers containing functional groups can also be used.

[0273] -Vinyl polymer adhesives composed of vinyl polymers-

[0274] There are no particular limitations on the vinyl polymer used to form the vinyl polymer adhesive, and preferred vinyl polymers for forming the adhesive-forming polymer P1 of the aforementioned low-adsorption adhesive PB1 can be cited. For example, polymers containing, for instance, 50 mol% or more or 50 wt% or more of vinyl monomers other than the (meth)acrylic acid compound described later can be cited. As vinyl monomers, the aforementioned vinyl compounds can be cited. Specifically, as vinyl polymers, examples include polyvinyl alcohol, polyvinyl acetal, polyvinyl acetate, or copolymers containing these.

[0275] The vinyl polymer preferably contains, in addition to components derived from vinyl monomers, components derived from (meth)acrylic acid compounds. The content of the components derived from vinyl monomers is preferably the same as the content of the components derived from (meth)acrylic acid compounds (M1) in the following (meth)acrylic acid polymers. The content of the components derived from (meth)acrylic acid compounds in the polymer is not particularly limited as long as it is less than 50% by mass, and is preferably 0-30% by mass.

[0276] -A (meth)acrylic polymer adhesive composed of (meth)acrylic polymers-

[0277] There are no particular limitations on the (meth)acrylic polymer used to form the (meth)acrylic polymer adhesive, and preferred (meth)acrylic polymers used as adhesive forming polymers P1 for forming the aforementioned low-adsorption adhesive PB1 are given. For example, polymers obtained by copolymerizing at least one (meth)acrylic compound (M4) selected from (meth)acrylic compounds, (meth)acrylic ester compounds, (meth)acrylamide compounds, and (meth)acrylonitrile compounds are preferred. This (meth)acrylic compound (M4) is the same as the aforementioned (meth)acrylic compound (M1) except that it contains (meth)acrylic compounds. Furthermore, (meth)acrylic polymers composed of copolymers of (meth)acrylic compound (M4) and other polymerizable compounds (M3) are also preferred. As (meth)acrylic ester compounds, alkyl (meth)acrylic ester compounds can be given as examples, and the number of carbon atoms in the alkyl group is not particularly limited, for example, it can be set to 1 to 24, preferably 3 to 20, more preferably 4 to 16, and even more preferably 6 to 14. Furthermore, two or more alkyl (meth)acrylate compounds can be used, such as combinations of the aforementioned single-chain or cyclic alkyl (meth)acrylate compounds and the aforementioned alkyl (meth)acrylate compounds, or combinations of the aforementioned alkyl (meth)acrylate compounds and acrylamide compounds. There are no particular limitations on other polymerizable compounds (M3), and examples include styrene compounds, vinylnaphthalene compounds, vinyl carbazole compounds, allyl compounds, vinyl ether compounds, vinyl ester compounds, itaconic acid dialkyl compounds, unsaturated carboxylic anhydrides, and other vinyl compounds. Examples of vinyl compounds include, for instance, the "ethylene monomers" described in Japanese Patent Application Publication No. 2015-88486.

[0278] The content of the constituent components derived from the (meth)acrylic acid compound in the (meth)acrylic acid polymer is preferably the same as the content of the constituent components derived from the (meth)acrylic acid compound (M1) in the (meth)acrylic acid polymer. Furthermore, the content of other polymerizable compounds (M3) in the (meth)acrylic acid polymer is not particularly limited, and can be, for example, set to less than 50 mol% or less than 50 wt%.

[0279] There is no particular limitation on the content of the chain polymer binder PB3 in the composition containing inorganic solid electrolyte. From the viewpoint of being able to improve dispersion stability, operability and current collector adhesion in a balanced manner, it is preferably 0.02 to 15.0% by mass of the solid component in 100% by mass, more preferably 0.05 to 10.0% by mass, and even more preferably 0.1 to 7.0% by mass.

[0280] (Combination of polymer adhesive PB)

[0281] The polymer binder PB contained in the composition containing inorganic solid electrolyte of the present invention may include at least one low-adsorption binder PB1, or more than two, as described above.

[0282] Examples of polymer adhesives comprising the low-adsorption adhesive PB1 include: comprising only the low-adsorption adhesive PB1; comprising two or more low-adsorption adhesives PB1; comprising one or more low-adsorption adhesives PB1 and particulate adhesive PB2; and further comprising a chain-polymer adhesive PB3. Preferably, the polymer adhesive comprises one or more low-adsorption adhesives PB1 and one or more chain-polymer adhesives PB3. In all the above embodiments, the specific combination of each polymer adhesive is not particularly limited, but a combination of preferred combinations of each polymer adhesive is preferred.

[0283] In this invention, the chain polymer adhesive PB3 contained in the polymer adhesive PB can be at least one of hydrocarbon polymer adhesive, vinyl polymer adhesive and (meth)acrylic polymer adhesive, preferably (meth)acrylic polymer adhesive.

[0284] <Dispersion Medium>

[0285] The inorganic solid electrolyte composition of the present invention contains a dispersion medium that disperses or dissolves the above-mentioned components.

[0286] As a dispersion medium, any organic compound that appears as a liquid in the environment can be used, such as various organic solvents. Specifically, examples include alcohols, ethers, amides, amines, ketones, aromatics, aliphatic compounds, nitriles, and esters.

[0287] The dispersion medium can be a nonpolar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium). From the viewpoint of exhibiting excellent dispersibility, a nonpolar dispersion medium is preferred. A nonpolar dispersion medium generally refers to a medium with low affinity for water; however, in this invention, examples include ester compounds, ketone compounds, ether compounds, aromatic compounds, and aliphatic compounds, among which ketone compounds, aliphatic compounds, and ester compounds are preferred.

[0288] Examples of alcohol compounds include, for example, methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.

[0289] Examples of ether compounds include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl ether, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxanes (including 1,2-, 1,3- and 1,4- isomers, etc.)).

[0290] Examples of amide compounds include, for example, N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, hexamethylphosphoric triamide, etc.

[0291] Examples of amine compounds include triethylamine, diisopropylethylamine, and tri-n-butylamine.

[0292] Examples of ketone compounds include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutylpropyl ketone, sec-butylpropyl ketone, pentylpropyl ketone, butylpropyl ketone, etc.

[0293] Examples of aromatic compounds include, for example, benzene, toluene, xylene, and perfluorotoluene.

[0294] Examples of aliphatic compounds include hexane, heptane, octane, nonane, decane, dodecane, cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, decahydronaphthalene, paraffin wax, gasoline, naphtha, kerosene, and light oil.

[0295] Examples of nitrile compounds include acetonitrile, propionitrile, and isobutyronitrile.

[0296] Examples of ester compounds include, for example, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, pentyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl neovalerate, isopropyl neovalerate, butyl neovalerate, isobutyl neovalerate, etc.

[0297] In this invention, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds, and ester compounds are preferred, and ester compounds, ketone compounds, aromatic compounds, or ether compounds are more preferred.

[0298] There is no particular limitation on the number of carbon atoms in the compound constituting the dispersion medium, but it is preferably 2 to 30, more preferably 4 to 20, even more preferably 6 to 15, and especially preferably 7 to 12.

[0299] The boiling point of the dispersion medium at atmospheric pressure (1 atmosphere) is preferably 50°C or higher, more preferably 70°C or higher. The upper limit is preferably 250°C or lower, and even more preferably 220°C or lower.

[0300] The inorganic solid electrolyte composition of the present invention may contain at least one dispersion medium, or it may contain two or more. Examples of containing two or more dispersion media include mixed xylenes (a mixture of o-xylene, p-xylene, m-xylene, and ethylbenzene).

[0301] In this invention, the content of the dispersion medium in the inorganic solid electrolyte composition is not particularly limited and can be appropriately set. For example, the inorganic solid electrolyte composition preferably contains 20-80% by mass, more preferably 30-70% by mass, and particularly preferably 40-60% by mass.

[0302] <Active Substances>

[0303] The inorganic solid electrolyte composition of the present invention preferably contains an active material capable of intercalating and deintercalating ions of metals belonging to Group 1 or Group 2 of the periodic table. Examples of active materials, including positive electrode active materials and negative electrode active materials, will be described below.

[0304] In this invention, an inorganic solid electrolyte composition containing an active material (positive electrode active material or negative electrode active material) is sometimes referred to as an electrode composition (positive electrode composition or negative electrode composition).

[0305] (Positive electrode active material)

[0306] The positive electrode active material is an active material capable of intercalating and deintercalating ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material capable of reversibly intercalating and deintercalating lithium ions. There are no particular limitations as long as the material has the above-mentioned characteristics, and it can be a transition metal oxide or organic matter from the decomposition battery, or an element that can recombine with Li, such as sulfur.

[0307] Among them, transition metal oxides are preferred as positive electrode active materials, and more preferably materials containing the transition metal element M. a A transition metal oxide (selected from one or more elements including Co, Ni, Fe, Mn, Cu, and V). Furthermore, element M may also be mixed into this transition metal oxide. b(Elements of Group 1(Ia) and Group 2(IIa) of the periodic table, excluding lithium, and elements such as Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B). As a mixing amount, it is preferable to be relative to the transition metal element M. a The amount (100 mol%) is 0-30 mol%. More preferably, it is Li / M a They are synthesized by mixing in a molar ratio of 0.3 to 2.2.

[0308] Specific examples of transition metal oxides include (MA) transition metal oxides with a layered rock salt structure, (MB) transition metal oxides with a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.

[0309] Specific examples of transition metal oxides (MA) with layered rock salt-type structures include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), and LiNi 0.85 Co 0.10 Al 0.05 O2 (lithium nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).

[0310] Specific examples of transition metal oxides (MB) with spinel-type structures include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.

[0311] Examples of lithium-containing transition metal phosphates (MC) include olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate).

[0312] Examples of lithium-containing transition metal halophosphates (MD) include, for example, iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.

[0313] Examples of lithium-containing transition metal silicate compounds include, for example, Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.

[0314] In this invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.

[0315] The shape of the positive electrode active material is not particularly limited, but particulate form is preferred. The particle size (volume average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1–50 μm. The particle size of the positive electrode active material can be measured in the same manner as the particle size of the aforementioned inorganic solid electrolyte. To achieve the desired particle size, a conventional pulverizer or classifier is used. For example, a mortar, ball mill, sand mill, vibratory ball mill, satellite ball mill, planetary ball mill, and rotary airflow jet mill or sieve can be suitably used. During pulverization, wet pulverization with a dispersion medium such as water or methanol can also be appropriately performed. To achieve the desired particle size, classification is preferred. Classification is not particularly limited and can be performed using sieves, air classifiers, etc. Both dry and wet classification can be used.

[0316] Positive active materials obtained by sintering can also be used after being cleaned with water, acidic aqueous solutions, alkaline aqueous solutions, and organic solvents.

[0317] One type of positive electrode active material can be used alone, or two or more types can be used in combination.

[0318] The content of the positive electrode active material in the inorganic solid electrolyte composition is not particularly limited, but it is preferably 10-97% by mass, more preferably 30-95% by mass, further preferably 40-93% by mass, and especially preferably 50-90% by mass in 100% by mass of the solid component.

[0319] (Negative electrode active material)

[0320] The negative electrode active material is an active material capable of intercalating and deintercalating ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material capable of reversibly intercalating and deintercalating lithium ions. There are no particular limitations on the material as long as it possesses the aforementioned properties; examples include carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, and negative electrode active materials capable of forming alloys with lithium (capable of alloying). From a reliability perspective, carbonaceous materials, metal composite oxides, or lithium monomers are preferred. From the viewpoint of enabling high-capacity all-solid-state secondary batteries, active materials capable of alloying with lithium are preferred.

[0321] Carbonaceous materials used as negative electrode active materials refer to materials that are essentially composed of carbon. Examples include carbonaceous materials produced by sintering petroleum asphalt, carbon black such as acetylene black (AB), graphite (natural graphite, vapor-grown graphite, and other artificial graphite), and various synthetic resins such as PAN (polyacrylonitrile) resins or furfuryl alcohol resins. Furthermore, examples include various types of carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol) carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as mesophase microspheres, graphite whiskers, and planar graphite.

[0322] These carbonaceous materials are classified into non-graphitized carbonaceous materials (also known as hard carbon) and graphitic carbonaceous materials based on the degree of graphitization. Furthermore, the carbonaceous materials preferably possess the facet spacing or density and crystallite size described in Japanese Patent Application Publication Nos. 62-22066, 2-6856, and 3-45473. The carbonaceous material need not be a single material; mixtures of natural and artificial graphite as described in Japanese Patent Application Publication No. 5-90844, or coated graphite as described in Japanese Patent Application Publication No. 6-4516, etc., can also be used.

[0323] As a carbonaceous material, hard carbon or graphite is preferred, with graphite being more preferred.

[0324] As oxides of metals or half-metals suitable as negative electrode active materials, there are no particular limitations as long as they are oxides capable of absorbing and releasing lithium. Examples include oxides of metal elements (metal oxides), composite oxides of metal elements, or composite oxides of metal elements and half-metal elements (collectively referred to as metal composite oxides), and oxides of half-metal elements (half-metal oxides). Among these oxides, amorphous oxides are preferred, and further preferred are chalcogenides, the reaction products of metal elements with elements of Group 16 of the periodic table. In this invention, a half-metal element refers to an element exhibiting intermediate properties between a metal element and a non-half-metal element, typically including six elements: boron, silicon, germanium, arsenic, antimony, and tellurium, and further including three elements: selenium, polonium, and astatine. Furthermore, amorphous refers to a material having a broad scattering band with vertices in the region of 20° to 40° at 2θ values ​​using CuKα X-ray diffraction, and may also have crystalline diffraction lines. The strongest intensity of the crystalline diffraction lines appearing in the region of 40° to 70° at a 2θ value is preferably 100 times or less than the intensity of the diffraction line at the apex of the broad scattering band appearing in the region of 20° to 40° at a 2θ value, more preferably 5 times or less, and especially preferably a non-crystalline diffraction line.

[0325] Among the compounds comprising the aforementioned amorphous oxides and chalcogenides, amorphous oxides of half-metallic elements or the aforementioned chalcogenides are more preferred, and (composite) oxides or chalcogenides comprising one or more elements selected from groups 13(IIIB) to 15(VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga₂O₃, GeO, PbO, PbO₂, Pb₂O₃, Pb₂O₄, Pb₃O₄, Sb₂O₄, Sb₂O₈Bi₂O₃, Sb₂O₈Si₂O₃, Sb₂O₅, Bi₂O₃, Bi₂O₄, GeS, PbS, PbS₂, Sb₂S₃, or Sb₂S₅.

[0326] As a negative electrode active material that can be used with amorphous oxides centered on Sn, Si, and Ge, carbonaceous materials, lithium monomers, lithium alloys, and negative electrode active materials that can be alloyed with lithium are preferred examples.

[0327] From the viewpoint of high current density charge and discharge characteristics, oxides of metal or half-metal elements, especially metal (composite) oxides and the aforementioned chalcogenides, preferably contain at least one of titanium and lithium as constituent components. Examples of lithium-containing metal composite oxides (lithium composite metal oxides) include composite oxides of lithium oxide with the aforementioned metal (composite) oxides or chalcogenides; more specifically, Li₂SnO₂ can be cited.

[0328] The negative electrode active material, such as a metal oxide, preferably contains titanium (titanium oxide). Specifically, due to Li4Ti5O 12 Lithium titanate (LTO) exhibits minimal volume change during lithium ion adsorption and deintercalation, resulting in excellent rapid charge and discharge characteristics. It is preferred in terms of both suppressing electrode degradation and improving the lifespan of lithium-ion secondary batteries.

[0329] There are no particular restrictions on the lithium alloy used as the negative electrode active material, as long as it is an alloy commonly used as the negative electrode active material in secondary batteries. For example, lithium-aluminum alloys can be cited. Specifically, lithium-aluminum alloys can be cited, which are made by adding 10% by mass of aluminum to lithium as the base metal.

[0330] There are no particular limitations on the negative electrode active material that can form an alloy with lithium, as long as it is a negative electrode active material commonly used in secondary batteries. Such active materials experience significant expansion and contraction during charging and discharging in all-solid-state secondary batteries, which accelerates the decline in cycle characteristics. However, the inorganic solid electrolyte composition of the present invention contains the aforementioned polymer binder, thus suppressing the decline in cycle characteristics. Examples of such active materials include (negative electrode) active materials (alloys, etc.) containing silicon or tin, and various metals such as Al and In. Preferably, negative electrode active materials containing silicon (silicon-containing active materials) are preferred, as they enable higher battery capacity. More preferably, silicon-containing active materials have a silicon content of 50 mol% or more of all constituent elements.

[0331] Generally, negative electrodes containing these active materials (e.g., Si negative electrodes containing silicon-containing active materials, Sn negative electrodes containing tin-containing active materials, etc.) can absorb more Li ions compared to carbon negative electrodes (graphite and acetylene black, etc.). That is, the amount of Li ions retained per unit mass increases. Therefore, the battery capacity (energy density) can be increased. Consequently, it has the advantage of extending battery operating time.

[0332] Examples of silicon-containing active materials include silicon materials such as Si and SiOx (0 < x ≤ 1), as well as silicon-containing alloys (e.g., LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or structured active materials (e.g., LaSi2 / Si) containing elements such as titanium, vanadium, chromium, manganese, nickel, copper, and lanthanum. Additionally, active materials containing silicon elements such as SnSiO3 and SnSiS3, and tin elements, are also included. Furthermore, SiOx can be used as a negative electrode active material (a half-metal oxide) itself, and since Si is generated through the operation of an all-solid-state secondary battery, it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.

[0333] Examples of anode active materials containing tin include those containing Sn, SnO, SnO2, SnS, SnS2, and the aforementioned silicon and tin elements. Furthermore, composite oxides with lithium oxide, such as Li2SnO2, can also be cited.

[0334] In this invention, the above-mentioned negative electrode active material can be used without particular limitation. However, from the viewpoint of battery capacity, it is preferable to use a negative electrode active material that can be alloyed with lithium. More preferably, it is the above-mentioned silicon material or silicon-containing alloy (an alloy containing silicon element). It is even more preferably to contain silicon (Si) or a silicon-containing alloy.

[0335] As a determination method, inductively coupled plasma (ICP) emission spectroscopy can be used. As a simple method, the chemical formula of the compound obtained by the above-mentioned firing method can be calculated from the mass difference of the powder before and after firing.

[0336] The shape of the negative electrode active material is not particularly limited, but particulate form is preferred. The particle size (volume average particle size) of the negative electrode active material is not particularly limited, but is preferably 0.1–60 μm. The particle size of the negative electrode active material can be measured in the same manner as that of the inorganic solid electrolyte described above. To achieve the specified particle size, a conventional pulverizer or classifier is used, similar to that used for the positive electrode active material.

[0337] The above-mentioned negative electrode active material can be used alone or in combination of two or more.

[0338] The content of the negative electrode active material in the inorganic solid electrolyte composition is not particularly limited, but is preferably 10-90% by mass, more preferably 20-85% by mass, more preferably 30-80% by mass, and even more preferably 40-75% by mass in 100% by mass of solid components.

[0339] In this invention, when the negative electrode active material layer is formed by charging a secondary battery, ions of metals belonging to Group 1 or Group 2 of the periodic table generated within the all-solid-state secondary battery can be used instead of the aforementioned negative electrode active material. By bonding these ions with electrons and depositing them as metal, the negative electrode active material layer can be formed.

[0340] (Coating of active substances)

[0341] The surfaces of both the positive and negative electrode active materials can be coated with different metal oxides. Examples of surface coating agents include metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si, or Li. Specifically, examples include spinel titanate, tantalum oxides, niobium oxides, and lithium niobate compounds; for instance, Li₄Ti₅O₅ can be used. 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc.

[0342] Furthermore, the electrode surface containing positive or negative active materials can be surface-treated with sulfur or phosphorus.

[0343] Furthermore, the particle surfaces of the positive or negative active materials can be surface-treated by photochemical rays or active gases (such as plasma) before and after the aforementioned surface coating.

[0344] <Conductive additives>

[0345] The inorganic solid electrolyte composition of the present invention preferably contains a conductive additive, for example, a silicon-containing active material as a negative electrode active material is used in combination with the conductive additive.

[0346] There are no particular restrictions on the conductive additives used; any conductive additives known to be used as conductive additives can be used. For example, they can be graphite materials such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, and furnace black, amorphous carbon such as needle coke, carbon fiber materials such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, metal powders such as copper and nickel, metal fibers, or conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives.

[0347] In this invention, when active materials and conductive additives are used in combination, the conductive additives that do not produce the insertion and extraction of metal ions (preferably Li ions) belonging to Group I or Group II of the periodic table during battery charging and discharging, and do not function as active materials, are classified as conductive additives. Therefore, among conductive additives, those that can function as active materials in the active material layer during battery charging and discharging are classified as active materials rather than conductive additives. Whether an additive functions as an active material during battery charging and discharging is determined by its combination with active materials, rather than by a general rule.

[0348] The conductive additive may contain one type or two or more types.

[0349] There are no particular restrictions on the shape of the conductive additive, but it is preferably in particulate form.

[0350] When the inorganic solid electrolyte composition of the present invention contains a conductive additive, the content of the conductive additive in the inorganic solid electrolyte composition is preferably 0 to 10% by mass of 100% by mass of the solid component.

[0351] <Lithium Salts>

[0352] The inorganic solid electrolyte composition of the present invention preferably also contains a lithium salt (supporting electrolyte).

[0353] As a lithium salt, the lithium salt commonly used in this product is preferred, and there are no particular restrictions. For example, the lithium salt described in paragraphs 0082 to 0085 of Japanese Patent Application Publication No. 2015-088486 is preferred.

[0354] When the inorganic solid electrolyte composition of the present invention contains a lithium salt, the content of the lithium salt relative to 100 parts by weight of the solid electrolyte is preferably 0.1 parts by weight or more, more preferably 5 parts by weight or more. As an upper limit, it is preferably 50 parts by weight or less, more preferably 20 parts by weight or less.

[0355] <Dispersant>

[0356] In the inorganic solid electrolyte composition of the present invention, the aforementioned low-adsorption binder PB1 also functions as a dispersant; therefore, it may or may not contain any dispersant other than the low-adsorption binder PB1. As a dispersant, a dispersant commonly used in all-solid-state secondary batteries can be appropriately selected. Typically, compounds suitable for particle adsorption, steric hindrance, and / or electrostatic repulsion are appropriately used.

[0357] <Other Additives>

[0358] The inorganic solid electrolyte composition of the present invention can appropriately contain ionic liquids, thickeners, crosslinking agents (substances that undergo crosslinking reactions via free radical polymerization, condensation polymerization, or ring-opening polymerization, etc.), polymerization initiators (substances that generate acids or free radicals through heat or light, etc.), defoamers, homogenizers, dehydrating agents, antioxidants, etc., as other components besides those mentioned above. The ionic liquid is a liquid contained to further improve ionic conductivity, and known liquids can be used without particular limitation. Furthermore, it can contain polymers other than the aforementioned binder-forming polymers, commonly used adhesives, etc.

[0359] (Preparation of inorganic solid electrolyte compositions)

[0360] The inorganic solid electrolyte composition of the present invention can be prepared, for example, by mixing an inorganic solid electrolyte, the aforementioned polymer binder PB, a dispersion medium, preferably a conductive additive, and a suitable lithium salt, and any other components, as a mixture, preferably as a slurry, using various commonly used mixers. In the case of the electrode composition, an active material is further mixed in.

[0361] There are no particular limitations on the mixing method; any known mixer, such as a ball mill, bead mill, planetary mixer, scraper mixer, roller mill, kneader, disc mill, rotary-revolutionary mixer, or narrow-gap disperser, can be used. The components can be mixed all at once or sequentially. There are no particular limitations on the mixing environment; dry air or inert gas conditions are acceptable. Furthermore, there are no particular limitations on the mixing conditions, which can be appropriately set.

[0362] [Sheets for all-solid-state rechargeable batteries]

[0363] The sheet material for all-solid-state secondary batteries of the present invention is a sheet-shaped molded body capable of forming the constituent layers of an all-solid-state secondary battery, and includes various forms depending on its application. For example, sheets preferably used for solid electrolyte layers (also called solid electrolyte sheets for all-solid-state secondary batteries) and sheets preferably used for electrodes or laminates of electrodes and solid electrolyte layers (electrode sheets for all-solid-state secondary batteries) are examples. In the present invention, these various sheets are collectively referred to as sheets for all-solid-state secondary batteries.

[0364] In this invention, each layer constituting the sheet for all-solid-state secondary batteries can be a single-layer structure or a multi-layer structure.

[0365] In the sheet for all-solid-state secondary batteries, the solid electrolyte layer or the active material layer on the substrate is formed from the inorganic solid electrolyte composition of the present invention. Therefore, this sheet for all-solid-state secondary batteries can be used as the solid electrolyte layer of an all-solid-state secondary battery by appropriately peeling off the substrate, or directly as an electrode (a laminate of current collector and active material layer), thereby improving the cycle characteristics and conductivity (low resistance) of the all-solid-state secondary battery.

[0366] The solid electrolyte sheet for all-solid-state secondary batteries of the present invention can be any sheet having a solid electrolyte layer. It can be a sheet with the solid electrolyte layer formed on a substrate, or it can be a sheet without a substrate, formed from the solid electrolyte layer (a sheet obtained by peeling off the substrate). The solid electrolyte sheet for all-solid-state secondary batteries may have other layers besides the solid electrolyte layer. Examples of other layers include a protective layer (release sheet), a current collector, and a coating. Examples of the solid electrolyte sheet for all-solid-state secondary batteries of the present invention include a sheet having, in sequence on a substrate, a layer composed of the inorganic solid electrolyte composition of the present invention, a conventional solid electrolyte layer, and a protective layer. The solid electrolyte layer of the solid electrolyte sheet for all-solid-state secondary batteries is formed from the inorganic solid electrolyte composition of the present invention. The content of each component in this solid electrolyte layer is not particularly limited; preferred meanings are the same as the content of each component in the solid component of the inorganic solid electrolyte composition of the present invention. The layer thickness of each layer constituting the solid electrolyte sheet for all-solid-state secondary batteries is the same as the layer thickness described later in the description of all-solid-state secondary batteries.

[0367] As for the substrate, there are no particular limitations as long as it is a substrate capable of supporting the solid electrolyte layer. Examples include sheet-like materials (plate-like bodies) such as those described in the current collector section (described later), organic materials, and inorganic materials. Examples of organic materials include various polymers, specifically polyethylene terephthalate, polypropylene, polyethylene, and cellulose. Examples of inorganic materials include, for example, glass and ceramics.

[0368] The electrode sheet for all-solid-state secondary batteries of the present invention (also simply referred to as "electrode sheet") can be any electrode sheet having an active material layer. It can be a sheet with the active material layer formed on a substrate (current collector), or a sheet formed from the active material layer without a substrate (a sheet obtained by peeling off the substrate). The electrode sheet is typically a sheet having a current collector and an active material layer, but it also includes forms having a current collector, an active material layer, and a solid electrolyte layer in sequence, and forms having a current collector, an active material layer, a solid electrolyte layer, and an active material layer in sequence. The solid electrolyte layer and active material layer of the electrode sheet are preferably formed from the inorganic solid electrolyte composition of the present invention. The content of each component in the solid electrolyte layer or active material layer is not particularly limited, and the preferred meaning has the same meaning as the content of each component in the solid component of the inorganic solid electrolyte composition (electrode composition) of the present invention. The layer thickness of each layer constituting the electrode sheet of the present invention is the same as the layer thickness described later in the description of all-solid-state secondary batteries. The electrode sheet may have the other layers mentioned above.

[0369] In addition, when the solid electrolyte layer or active material layer is not formed by the inorganic solid electrolyte composition of the present invention, it is formed by a conventional constituent layer forming material.

[0370] In the all-solid-state secondary battery sheet of the present invention, at least one of the solid electrolyte layer and the active material layer is formed from the inorganic solid electrolyte composition of the present invention, and has a surface-flat constituent layer that suppresses the increase of interfacial resistance between solid particles while firmly bonding the solid particles together. Therefore, the all-solid-state secondary battery sheet of the present invention, when used as a constituent layer of an all-solid-state secondary battery, enables the realization of low resistance (high conductivity) and excellent cycle characteristics of the all-solid-state secondary battery. In particular, in the all-solid-state secondary battery electrode sheet and the all-solid-state secondary battery in which the active material layer is formed by the inorganic solid electrolyte composition of the present invention, the active material layer and the current collector exhibit strong adhesion, which further improves the cycle characteristics. Therefore, the all-solid-state secondary battery sheet of the present invention is suitable as a sheet capable of forming a constituent layer of an all-solid-state secondary battery.

[0371] Furthermore, since the all-solid-state secondary battery sheet of the present invention can form a constituent layer that firmly bonds solid particles, it can also be manufactured by industrial manufacturing methods that allow external stress to act easily, such as the high-productivity roll-to-roll method.

[0372] [Manufacturing Method of Sheets for All-Solid-State Secondary Batteries]

[0373] The manufacturing method of the all-solid-state secondary battery sheet of the present invention is not particularly limited, and it can be manufactured by forming the above-mentioned layers using the inorganic solid electrolyte composition of the present invention. For example, a preferred method is to form a layer (coated and dried layer) composed of the inorganic solid electrolyte composition by film formation (coating and drying) on ​​a substrate or current collector (which may be via another layer). This allows the production of an all-solid-state secondary battery sheet having a substrate or current collector and a coated and dried layer. In particular, when the all-solid-state secondary battery sheet is produced by film formation of the inorganic solid electrolyte composition of the present invention on a current collector, the adhesion between the current collector and the active material layer can be enhanced. Here, the coated and dried layer refers to a layer formed by coating the inorganic solid electrolyte composition of the present invention and drying the dispersion medium (i.e., a layer formed using the inorganic solid electrolyte composition of the present invention, and composed of a composition from which the dispersion medium is removed). The dispersion medium may remain in the active material layer and the coated and dried layer as long as it does not impair the effects of the present invention; the residual amount can be, for example, 3% by mass or less in each layer.

[0374] In the manufacturing method of the all-solid-state secondary battery sheet of the present invention, each step such as coating and drying will be described in the following manufacturing method of the all-solid-state secondary battery.

[0375] In the method for manufacturing the sheet material for all-solid-state secondary batteries of the present invention, the coated and dried layer obtained in the above manner can also be pressurized. The pressurization conditions, etc., will be explained in the manufacturing method for all-solid-state secondary batteries described later.

[0376] Furthermore, in the manufacturing method of the all-solid-state secondary battery sheet of the present invention, it is also possible to peel off the substrate, protective layer (especially the sheet), etc.

[0377] [All-solid-state rechargeable battery]

[0378] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The all-solid-state secondary battery of the present invention is only required to have a structure with a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer; other structures are not particularly limited, for example, known structures related to all-solid-state secondary batteries can be used. The positive electrode active material layer is preferably formed on a positive electrode current collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on a negative electrode current collector and constitutes the negative electrode.

[0379] In this invention, each constituent layer (including current collectors, etc.) constituting the all-solid-state secondary battery can be a single-layer structure or a multi-layer structure.

[0380] <Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer>

[0381] The solid electrolyte layer contains an inorganic solid electrolyte having conductivity of ions belonging to Group I or Group II of the periodic table, a polymer binder PB, and any of the above-mentioned components within the scope that does not impair the effects of the present invention, and generally does not contain positive electrode active materials and / or negative electrode active materials.

[0382] The positive electrode active material layer contains an inorganic solid electrolyte having conductivity of ions belonging to Group I or Group II of the periodic table, a polymer binder PB, a positive electrode active material, and any of the above-mentioned components within the scope that does not impair the effects of the present invention.

[0383] The negative electrode active material layer contains an inorganic solid electrolyte with conductivity of ions belonging to Group I or Group II of the periodic table, a polymer binder PB, a negative electrode active material, and any of the above-mentioned components within the scope that does not impair the effects of the present invention.

[0384] In the all-solid-state secondary battery of the present invention, at least one of the negative electrode active material layer, the positive electrode active material layer, and the solid electrolyte layer is formed by the inorganic solid electrolyte composition of the present invention. Preferably, the solid electrolyte layer or at least one of the negative electrode active material layer and the positive electrode active material layer is formed by the inorganic solid electrolyte composition of the present invention. It is also a preferred embodiment that all layers are formed by the inorganic solid electrolyte composition of the present invention. In the present invention, the constituent layers of the all-solid-state secondary battery formed by the inorganic solid electrolyte composition of the present invention refer to the manner in which the constituent layers are formed by the sheet for the all-solid-state secondary battery of the present invention (wherein, when there are layers other than those formed by the inorganic solid electrolyte composition of the present invention, the sheet is obtained by removing those layers).

[0385] Regarding the types and amounts of components contained therein, the active material layer or solid electrolyte layer formed by the inorganic solid electrolyte composition of the present invention is preferably the same as that in the solid components of the inorganic solid electrolyte composition of the present invention. Furthermore, when the active material layer or solid electrolyte layer is not formed by the inorganic solid electrolyte composition of the present invention, known materials can be used.

[0386] There are no particular limitations on the thickness of the negative electrode active material layer, the solid electrolyte layer, and the positive electrode active material layer. Considering the size of a typical all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is further preferably 50 μm or more and less than 500 μm.

[0387] The positive electrode active material layer and the negative electrode active material layer can each have a current collector on the side opposite to the solid electrolyte layer.

[0388] <Current Collector>

[0389] The positive and negative current collectors are preferably electron conductors.

[0390] In this invention, either the positive current collector or the negative current collector, or both of them together, are sometimes referred to simply as a current collector.

[0391] In addition to aluminum, aluminum alloys, stainless steel, nickel, and titanium, materials in which carbon, nickel, titanium, or silver (materials forming thin films) are treated on the surface of aluminum or stainless steel are preferred as the material forming the positive current collector. Among these, aluminum and aluminum alloys are more preferred.

[0392] In addition to aluminum, copper, copper alloys, stainless steel, nickel, and titanium, materials that have been treated with carbon, nickel, titanium, or silver on the surface of aluminum, copper, copper alloys, or stainless steel are preferred as materials for forming the negative current collector. More preferably, aluminum, copper, copper alloys, and stainless steel are preferred.

[0393] Current collectors are typically in the form of a membrane, but can also be made of mesh, perforated material, lath, porous material, foam, or fiber assembly.

[0394] There is no particular limitation on the thickness of the current collector, but it is preferably 1 to 500 μm. Furthermore, it is also preferable to have irregularities on the surface of the current collector through surface treatment.

[0395] <Other Structures>

[0396] In this invention, functional layers or components may be appropriately inserted or disposed between or on the outside of the layers of the negative electrode current collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode current collector.

[0397] <Frame>

[0398] The all-solid-state secondary battery of the present invention can be used as an all-solid-state secondary battery in the above-described structural state depending on the application, but in order to make it into a dry cell form, it is preferable to further enclose it in a suitable casing. The casing can be a metallic casing or a resin (plastic) casing. When using a metallic casing, for example, a casing made of aluminum alloy or stainless steel can be cited. Preferably, the metallic casing is divided into a positive electrode side casing and a negative electrode side casing, which are electrically connected to the positive electrode current collector and the negative electrode current collector, respectively. Preferably, the positive electrode side casing and the negative electrode side casing are joined together as one piece with a short-circuit prevention gasket.

[0399] <Preferred Implementation Method of All-Solid-State Secondary Battery>

[0400] The following is for reference. Figure 1 The preferred embodiments of the present invention will be described, but the present invention is not limited thereto.

[0401] Figure 1 This is a schematic cross-sectional view illustrating a preferred embodiment of the all-solid-state secondary battery (lithium-ion secondary battery) of the present invention. Viewed from the negative electrode side, the all-solid-state secondary battery 10 of this embodiment sequentially comprises a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode current collector 5. Each layer is in contact with the others and has an adjacent structure. By employing such a structure, electrons (electrons) are supplied to the negative electrode side during charging. - ), and accumulate lithium ions (Li) here. + On the other hand, during discharge, lithium ions (Li) accumulated at the negative electrode... + The electrons return to the positive side and supply electrons to the working part 6. In the illustrated example, a light bulb is used as a model in the working part 6, and the bulb is lit by discharging.

[0402] In having Figure 1 When the layered solid-state secondary battery shown is placed in a 2032-type button cell (e.g., reference...), Figure 2 Sometimes, this all-solid-state secondary battery is also called the all-solid-state secondary battery laminate 12. The battery made by placing the all-solid-state secondary battery laminate 12 in the 2032 type button battery box 11 is called (button type) all-solid-state secondary battery 13 for distinction.

[0403] (Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer)

[0404] In the all-solid-state secondary battery 10, the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer are all formed from the inorganic solid electrolyte composition of the present invention. This all-solid-state secondary battery 10 achieves excellent battery performance, namely, low resistance and excellent cycle characteristics. The inorganic solid electrolyte and polymer binder contained in the positive electrode active material layer 4, the solid electrolyte layer 3, and the negative electrode active material layer 2 can be of the same type or different types.

[0405] In this invention, either or both of the positive electrode active material layer and the negative electrode active material layer are simply referred to as the active material layer or the electrode active material layer. Furthermore, either or both of the positive electrode active material and the negative electrode active material are collectively referred to as the active material or the electrode active material.

[0406] In the all-solid-state secondary battery 10, the negative electrode active material layer can be a lithium metal layer. Examples of lithium metal layers include layers formed by stacking or molding lithium metal powder, lithium foil, and lithium vapor-deposited films. The thickness of the lithium metal layer is independent of the aforementioned thickness of the negative electrode active material layer, and for example, can be set to 1 to 500 μm.

[0407] In the all-solid-state secondary battery 10 described above, when it has a constituent layer other than the constituent layer formed by the inorganic solid electrolyte composition of the present invention, a layer formed by a known constituent layer forming material can also be used.

[0408] In this invention, when the constituent layer is formed from the inorganic solid electrolyte composition of this invention, an all-solid-state secondary battery with excellent cycle characteristics and low resistance can be achieved even when manufactured by an industrially advantageous roll-to-roll method.

[0409] (Current collector)

[0410] The positive current collector 5 and the negative current collector 1 are as described above.

[0411] [Manufacturing of all-solid-state rechargeable batteries]

[0412] All-solid-state secondary batteries can be manufactured using conventional methods. Specifically, all-solid-state secondary batteries can be manufactured by forming the aforementioned layers using the inorganic solid electrolyte composition of the present invention. This will be described in detail below.

[0413] The all-solid-state secondary battery of the present invention can be manufactured by performing a method (the method for manufacturing the sheet for all-solid-state secondary battery of the present invention) that includes a step of forming a coating film by appropriately coating the inorganic solid electrolyte composition of the present invention onto a substrate (e.g., a metal foil that serves as a current collector).

[0414] For example, a positive electrode active material layer is formed by coating an inorganic solid electrolyte composition containing a positive electrode active material as a positive electrode material (positive electrode composition) onto a metal foil serving as the positive electrode current collector to create a positive electrode sheet for an all-solid-state secondary battery. Next, an inorganic solid electrolyte composition for forming a solid electrolyte layer is coated onto this positive electrode active material layer to form a solid electrolyte layer. Furthermore, an inorganic solid electrolyte composition containing a negative electrode active material as a negative electrode material (negative electrode composition) is coated onto the solid electrolyte layer to form a negative electrode active material layer. By overlapping a negative electrode current collector (metal foil) onto the negative electrode active material layer, an all-solid-state secondary battery with a structure in which the solid electrolyte layer is sandwiched between the positive and negative electrode active material layers can be obtained. It can also be encapsulated in a casing to form a desired all-solid-state secondary battery.

[0415] Furthermore, in contrast to the methods for forming each layer, it is also possible to manufacture an all-solid-state secondary battery by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode current collector as a substrate and then overlapping a positive electrode current collector.

[0416] As another method, the following approach can be used: The positive electrode sheet for an all-solid-state secondary battery is manufactured as described above. Furthermore, an inorganic solid electrolyte composition containing negative electrode active material is coated onto a metal foil serving as the negative electrode current collector to form a negative electrode active material layer, thereby manufacturing the negative electrode sheet for an all-solid-state secondary battery. Next, a solid electrolyte layer is formed on the active material layer of any one of these sheets, as described above. Then, the positive electrode sheet for an all-solid-state secondary battery and another negative electrode sheet for an all-solid-state secondary battery are stacked on the solid electrolyte layer in such a way that the solid electrolyte layer and the active material layer are in contact. In this way, an all-solid-state secondary battery can be manufactured.

[0417] Furthermore, as another method, the following can be cited: That is, to manufacture the positive electrode sheet and the negative electrode sheet for an all-solid-state secondary battery as described above. In addition, a solid electrolyte sheet for an all-solid-state secondary battery, consisting of a solid electrolyte layer, is manufactured by coating an inorganic solid electrolyte composition onto a substrate. Moreover, the solid electrolyte layer, which has been peeled off from the substrate, is stacked in a manner where the positive electrode sheet and the negative electrode sheet for an all-solid-state secondary battery hold it in place. In this way, an all-solid-state secondary battery can be manufactured.

[0418] Furthermore, as described above, a positive electrode sheet, a negative electrode sheet, and a solid electrolyte sheet for an all-solid-state secondary battery are manufactured. Next, the positive or negative electrode active material layer and the solid electrolyte sheet are overlapped and pressurized. This transfers the solid electrolyte layer onto the positive or negative electrode sheet. Then, the solid electrolyte layer obtained by peeling off the substrate of the solid electrolyte sheet is overlapped with the negative or positive electrode sheet (while the negative or positive electrode active material layer is in contact with the solid electrolyte layer) and pressurized. In this way, an all-solid-state secondary battery can be manufactured. The pressing method and conditions in this method are not particularly limited, and the methods and conditions described in the pressing process described later can be used.

[0419] Solid electrolyte layers, for example, can also be formed by pressure molding under pressure conditions described later on a substrate or active material layer to form an inorganic solid electrolyte composition, and sheet molded articles of solid electrolytes or active materials can also be used.

[0420] In the above manufacturing method, the inorganic solid electrolyte composition of the present invention can be used for any one of the positive electrode composition, the inorganic solid electrolyte composition, and the negative electrode composition. It is preferred to use the inorganic solid electrolyte composition of the present invention for at least one of the inorganic solid electrolyte composition or the positive electrode composition and the negative electrode composition. It is also possible to use the inorganic solid electrolyte composition of the present invention for any composition.

[0421] When a solid electrolyte layer or active material layer is formed from a composition other than the inorganic solid electrolyte composition of the present invention, commonly used compositions can be cited as materials. Furthermore, in the manufacture of an all-solid-state secondary battery, instead of forming a negative electrode active material layer, ions of metals belonging to Group I or Group II of the periodic table accumulated in the negative electrode current collector during initialization or charging (described later) combine with electrons, and are deposited as metal on the negative electrode current collector, thereby forming a negative electrode active material layer.

[0422] <Formation of each layer (film formation)>

[0423] There are no particular limitations on the coating method for the inorganic solid electrolyte composition, and appropriate methods can be selected. Examples include coating (preferably wet coating), spraying, spin coating, dip coating, slot coating, strip coating, and bar coating.

[0424] At this point, the inorganic solid electrolyte composition can be dried after separate coating or after multi-layer coating. There are no particular limitations on the drying temperature. The lower limit is preferably 30°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. The upper limit is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower. By heating within this temperature range, the dispersion medium can be removed to obtain a solid state (coated drying layer). Furthermore, it avoids excessively high temperatures and damage to the components of the all-solid-state secondary battery, which is therefore preferable. As a result, the all-solid-state secondary battery exhibits excellent overall performance and achieves good adhesion and good ionic conductivity.

[0425] After coating with an inorganic solid electrolyte composition, the layers are overlapped to form a solid-state secondary battery, or after fabrication of an all-solid-state secondary battery, each layer or the all-solid-state secondary battery is pressurized. Examples of pressurization methods include hydraulic cylinder presses. There are no particular limitations on the pressurization pressure, but a range of 5 to 1500 MPa is generally preferred.

[0426] Furthermore, the coated inorganic solid electrolyte composition can be heated simultaneously with pressurization. There are no particular limitations on the heating temperature, which is generally in the range of 30 to 300°C. Stamping can also be performed at temperatures higher than the glass transition temperature of the inorganic solid electrolyte. Additionally, stamping can also be performed at temperatures higher than the glass transition temperature of the polymer contained in the polymer binder. However, the temperature is generally no higher than the melting point of the polymer.

[0427] Pressurization can be performed either with the solvent or dispersion medium pre-dried or with residual solvent or dispersion medium remaining.

[0428] Alternatively, the various compositions can be coated simultaneously, or the coating, drying, and stamping can be performed simultaneously and / or sequentially. They can be laminated by transfer printing after being coated onto their respective substrates.

[0429] There are no particular restrictions on the atmosphere used in film-forming methods (coating, drying, pressurization (under heating)). It can be any atmosphere, including atmospheric pressure, dry air (dew point below -20°C), or inert gases (e.g., argon, helium, nitrogen).

[0430] The stamping time can be either a short period of time (e.g., within a few hours) to apply high pressure, or a long period of time (more than one day) to apply medium pressure. In the case of solid-state secondary batteries, except for sheets for all-solid-state secondary batteries, medium pressure can be continuously applied using the constraint tools of all-solid-state secondary batteries (such as screw tightening pressure).

[0431] Compared to the pressure-bearing parts such as the surface of the sheet, the stamping pressure can be uniform or varying.

[0432] The stamping pressure can be varied according to the area or film thickness of the pressed part. Furthermore, it is also possible to apply different pressures to the same part in stages.

[0433] The stamped surface can be smooth or rough.

[0434] <Initialization>

[0435] All-solid-state secondary batteries manufactured in the manner described above are preferably initialized after manufacturing or before use. There are no particular limitations on initialization; for example, initial charging and discharging can be performed under increased stamping pressure, followed by releasing the pressure until the normal operating pressure of the all-solid-state secondary battery is reached.

[0436] Applications of all-solid-state rechargeable batteries

[0437] The all-solid-state secondary battery of this invention is applicable to a wide variety of uses. There are no particular limitations on its application; for example, when incorporated into electronic devices, it can be used in laptops, pen-and-paper computers, mobile computers, e-book readers, mobile phones, cordless phones, pagers, handheld terminals, portable fax machines, portable copiers, portable printers, stereo headphones, camcorders, LCD TVs, portable vacuum cleaners, portable CD players, mini disk drives, electric shavers, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, etc. As other civilian products, it can be used in automobiles (electric vehicles), electric vehicles, motors, lighting fixtures, toys, game consoles, load conditioners, clocks, flashlights, cameras, and medical devices (pacemakers, hearing aids, and shoulder massagers, etc.). Furthermore, it can be used in various military and aerospace applications. It can also be combined with solar cells.

[0438] Example

[0439] The present invention will now be described in further detail with reference to embodiments, but the invention is not limited thereto. In the following embodiments, unless otherwise specified, "parts" and "%" of composition refer to mass. In the present invention, "room temperature" refers to 25°C.

[0440] 1. Polymer synthesis and preparation of adhesive solutions or dispersions

[0441] The following synthesis of the following chemical formulas and the binder forming polymers shown in Table 1 were used to prepare binder solutions or dispersions.

[0442] [Synthetic Example S-1: Synthesis of Polymer S-1 and Preparation of Adhesive Solution S-1]

[0443] Add 0.75 g of cuprous chloride and 22.7 g of acetonitrile to a 200 mL three-necked flask, dissolve the cuprous chloride, and bubble with nitrogen gas. Add 0.36 g of diethyl meso-2,5-dibromoadacic acid and 34.6 g of n-butyl acrylate bubbling with nitrogen gas. After heating to 80 °C, add 0.55 g of pentamethyldiethylenetriamine. Stir at 80 °C under a nitrogen gas flow. Cool and stop the reaction when the monomer reaction rate exceeds 80%.

[0444] The obtained reaction solution was added to 1.5 L of ice-cold methanol and purified by reprecipitation. The mixture was decanted, and the obtained polymer was decanted with ice-cold methanol. The above reprecipitation operation was repeated by dissolving in toluene until the residual monomer content relative to the polymer was less than 1% by mass. After confirming that the residual monomer content relative to the polymer was less than 1% by mass, the polymer was dissolved in toluene, and methanol was removed by solvent distillation to obtain the first block polymer solution (adjusted to 50% solids).

[0445] 20.0 g of the first block polymer solution (10.0 g solid), 0.03 g of cuprous chloride, 6.0 g of acetonitrile, and 24.0 g of toluene were added to a 200 mL three-necked flask and dissolved. 20.0 g of methyl methacrylate was then added, and the mixture was heated to 80 °C. 0.05 g of pentamethyldiethylenetriamine was added, and the mixture was stirred at 80 °C under a nitrogen stream. The reaction rate was tracked by nuclear magnetic resonance (NMR) spectroscopy, and the reaction time was adjusted to achieve the composition described in Table 1. The resulting reaction solution was added to 1 L of methanol and purified by reprecipitation. The mixture was decanted, and the polymer was dissolved in butyl butyrate. Methanol was removed by solvent distillation to obtain the block polymer solution.

[0446] Thus, polymer S-1 (an ABA-type block copolymer of (meth)acrylic acid polymer) that forms polymer P1 as an adhesive was synthesized, and a solution S-1 (concentration 10% by mass) of adhesive composed of this polymer was obtained.

[0447] [Synthetic Examples S-2~S-13, S-16~S-18, T-4: Synthesis of polymers S-2~S-13, S-16~S-18 and T-4 and preparation of adhesive solutions S-2~S-13, S-16~S-18 and T-4]

[0448] In Synthesis Example S-1, polymers S-2 to S-13, S-16 to S-18 and T-4 were introduced with compounds of each constituent component in such a way that they became the chemical formulas shown below and the compositions (content of constituent components) shown in Table 1. The polymerization reaction time was further adjusted appropriately. Otherwise, polymers S-2 to S-13, S-16 to S-18 and T-4 (all of which are (meth)acrylic acid polymers of ABA-type block copolymers) were synthesized in the same manner as in Synthesis Example S-1, and solutions of adhesives composed of each polymer, S-2 to S-13, S-16 to S-18 and T-4, were obtained.

[0449] In addition, when each polymer segment contains more than two constituent components, these constituent components are bonded in a random bonding manner.

[0450] Furthermore, the component of segment B in polymer S-13, derived from maleic anhydride monomethyl ether, is formed by methylating the cyclic dicarboxylic acid rod group through post-polymerization treatment.

[0451] [Synthetic Example S-14: Synthesis of Polymer S-14 and Preparation of Adhesive Solution S-14]

[0452] In a nitrogen-purged and dry pressure vessel, 300 g of cyclohexane as solvent and 0.3 mL of sec-butyllithium (1.3 M (mol / L), manufactured by FUJIFILM Wako Pure Chemical Corporation) as polymerization initiator were added. The mixture was heated to 50°C, and 9.0 g of styrene was added, followed by polymerization for 2 hours. Then, 52.2 g of 1,3-butadiene was added, and polymerization continued for 3 hours. Finally, 9.0 g of styrene was added, and polymerization continued for 2 hours. The resulting solution was precipitated again in methanol, and the solid was dried to obtain the polymer. Then, in a pressure vessel, the obtained polymer was completely dissolved in 400 parts by mass of cyclohexane. 5% by mass palladium on carbon (palladium loading: 5% by mass) was added as a hydrogenation catalyst, and the reaction was carried out for 10 hours at a hydrogen pressure of 2 MPa and 150°C. After cooling and depressurization, the palladium on carbon was removed by filtration, the filtrate was concentrated, and the solid obtained by vacuum drying was dissolved in butyl butyrate.

[0453] Thus, by synthesizing polymer S-14 (a hydrocarbon polymer of ABA-type block copolymer (SEBS)), a solution S-14 (concentration 10% by mass) of an adhesive composed of this polymer was obtained.

[0454] [Synthetic Example S-15: Synthesis of Polymer S-15 and Preparation of Adhesive Solution S-15]

[0455] Specifically, 200 parts by mass of ion-exchanged water, 100 parts by mass of vinylidene fluoride, 58 parts by mass of hexafluoropropylene, and 24 parts by mass of tetrafluoroethylene were added to an autoclave, along with 1 part by mass of diisopropyl peroxide dicarbonate. The mixture was stirred at 45°C for 10 hours. After polymerization, the precipitate was filtered and dried at 100°C for 10 hours to obtain polymer (binder) S-15.

[0456] Thus, polymer S-15 (a fluoropolymer of random copolymer) was synthesized, and this polymer was dissolved in butyl butyrate to obtain a solution S-15 (concentration 10% by mass) of an adhesive composed of polymer S-15.

[0457] [Synthetic Example S-19: Synthesis of Polymer S-19 and Preparation of Adhesive Solution S-19]

[0458] In Synthesis Example S-1, 0.36 g of diethyl meso-2,5-dibromoadipate was replaced with 0.20 g of ethyl 2-bromoisobutyrate. Compounds of each constituent component were introduced in such a manner that polymer S-19 becomes the chemical formula shown below and the composition (content of constituent components) shown in Table 1. The polymerization reaction time was further adjusted appropriately. Otherwise, polymer S-19 was synthesized in the same manner as in Synthesis Example S-1, and a solution S-19 of adhesive composed of each polymer was obtained.

[0459] Thus, by synthesizing polymer S-19 (an AB-type block copolymer of (meth)acrylic acid polymer), a solution S-19 (concentration 10% by mass) of an adhesive composed of this polymer was obtained.

[0460] [Synthetic Example T-1: Synthesis of Polymer T-1 and Preparation of Adhesive Dispersion T-1]

[0461] Add 3.7 g of polyethylene glycol (PEG200, number average molecular weight 200, manufactured by FUJIFILM Wako Pure Chemical Corporation), 3.7 g of polytetramethylene ether glycol (number average molecular weight 250, manufactured by SIGMA-Aldrich), and 4.1 g of NISSO-PB GI-1000 (trade name, manufactured by Nippon Soda Co., Ltd.) to a 300 mL three-necked flask, and dissolve them in 82.3 g of THF (tetrahydrofuran). Add 9.3 g of diphenylmethane diisocyanate (manufactured by FUJIFILM Wako Pure Chemical Corporation) to this solution and stir at 60 °C until homogeneous.

[0462] 65 mg of NEOSTANNU-600 (trade name, manufactured by Nitto Kasei Co., Ltd.) was added to the obtained solution, and the mixture was stirred at 60 °C for 5 hours. 0.96 g of methanol was added to the solution, and the polymer end was sealed to stop the polymerization reaction, yielding a 20% by mass THF solution (polymer solution) of polymer T-1.

[0463] (Preparation of adhesive dispersion T-1)

[0464] 15.00 g of the polymer solution obtained above was diluted with 15.00 g of THF. While stirring, 50.00 g of butyl butyrate was added dropwise over 1 hour, followed by concentration. Butyrate was then added again to achieve a concentration of 10%, and the concentration was adjusted. This synthesized polymer T-1 (urethane polymer), yielding a dispersion T-1 (concentration 10% by mass) of the adhesive composed of this polymer. The average particle size of the particulate adhesive in this dispersion was 120 nm.

[0465] [Synthesis Example T-2: Synthesis of Polymer T-2 and Preparation of Adhesive Solution T-2]

[0466] A monomer solution was prepared by adding 7.2 g of methyl methacrylate, 28.8 g of butyl acrylate, and 0.21 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako Pure Chemical Corporation) to a 100 mL volumetric flask and dissolving it in 27 g of butyl butyrate. 27 g of butyl butyrate was then added dropwise to a 300 mL three-necked flask, and the monomer solution was added dropwise over 2 hours at 80 °C with stirring. After the addition was complete, the temperature was raised to 90 °C, and the polymer solution (concentration 40% by mass) obtained after stirring for 2 hours was diluted with butyl butyrate to a concentration of 10%.

[0467] Thus, by synthesizing polymer T-2 (a random copolymer of (meth)acrylic acid polymer), a solution T-2 (concentration 10% by mass) of an adhesive composed of this polymer was obtained.

[0468] [Synthetic Example T-3: Synthesis of Polymer T-3 and Preparation of Adhesive Solution T-3]

[0469] In Synthesis Example T-2, compounds that introduce each constituent component are used to make polymer T-3 have the following chemical formula and composition as shown in Table 1 (types and amounts of constituent components). Otherwise, polymer T-3 (random copolymer (meth)acrylic polymer) is synthesized in the same manner as in Synthesis Example T-2, and a solution T-3 of adhesive composed of the polymer is obtained.

[0470] [Synthetic Example T-5: Synthesis of Polymer T-5 and Preparation of Adhesive Dispersion T-5]

[0471] In Synthesis Example S-1, 0.36 g of diethyl meso-2,5-dibromoadacic acid was replaced with 0.20 g of ethyl 2-bromoisobutyrate, and acetonitrile was replaced with dimethylformamide. The compounds of each constituent component were introduced in such a way that polymer T-5 was respectively the chemical formulas shown below and the composition (content of constituent components) shown in Table 1. The polymerization reaction time was further adjusted appropriately. Otherwise, polymer T-5 ((meth)acrylic acid polymer of AB type block copolymer) was synthesized in the same manner as in Synthesis Example S-1, and a dispersion T-5 (concentration 10% by mass) of the adhesive composed of this polymer was obtained.

[0472] 2. Synthesis of particulate adhesive Lx-1 and preparation of particulate adhesive dispersion Lx-1

[0473] [Synthetic Example Lx-1]

[0474] Add the following to a 2L three-necked flask equipped with a reflux condenser and a gas inlet plug: 7.2g of a 40% by mass heptane solution of macromonomer M-1, 12.4g of methyl acrylate (MA), 6.7g of acrylic acid (AA), 207g of heptane (manufactured by Wako Pure Chemical Corporation), and 1.4g of azoisobutyronitrile. Introduce nitrogen gas at a flow rate of 200mL / min for 10 minutes, then heat to 100°C. After 4 hours, add dropwise a liquid prepared separately (a mixture of 846g of a 40% by mass heptane solution of macromonomer M-1, 222.8g of methyl acrylate, 75.0g of acrylic acid, 300.0g of heptane, and 2.1g of azoisobutyronitrile). After the addition is complete, add 0.5g of azoisobutyronitrile. Then, after stirring at 100°C for 2 hours, the mixture was cooled to room temperature and filtered to synthesize acrylic polymer Lx-1, which forms the particulate binder PB2. A particulate binder dispersion Lx-1 (concentration 39.2% by mass) composed of this acrylic polymer was prepared. The tensile permanent deformation of acrylic polymer Lx-1 could not be determined (by the method described below). The average particle size of the particulate binder PB2 in this dispersion was 180 nm. The adsorption rate A of inorganic solid electrolyte in butyl butyrate was... SE It is 86%.

[0475] (Example of synthesis of macromonomer M-1)

[0476] A macromonomer M-1 was obtained by reacting a self-condensation compound (GPC polystyrene standard number-average molecular weight: 2,000) of glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 12-hydroxystearic acid (manufactured by Wako Pure Chemical Corporation) with acrylic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation). This polymer, obtained by polymerizing the resulting compound with methyl methacrylate and glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) in a molar ratio of 1:0.99:0.01, was then reacted with acrylic acid. The number-average molecular weight of macromonomer M-1 is 11,000.

[0477] 3. Synthesis of chain polymers SA-1 to SA-5 and preparation of chain polymer adhesive solutions SA-1 to SA-5

[0478] [Synthesis example SA-1]

[0479] 17.0 g of butyl butyrate was added to a 300 mL three-necked flask equipped with a reflux condenser and a gas inlet plug. Nitrogen gas was introduced at a flow rate of 50 mL / min for 30 minutes, and the temperature was raised to 80 °C. A liquid prepared in a separate container (a mixture of 9.5 g of methyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 25.2 g of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 1.1 g of hydroxyethyl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.2 g of maleic anhydride (manufactured by FUJIFILM Wako Pure Chemical Corporation), 10.0 g of butyl butyrate, and 0.04 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako Pure Chemical Corporation)) was then added dropwise over 4 hours. The mixture was then stirred at 80 °C for 2 hours, heated to 90 °C and stirred further for 2 hours, and finally cooled to room temperature to stop the reaction. The obtained reaction solution was added to 1 L of methanol and purified by reprecipitation. The mixture was decanted, the obtained polymer was washed with methanol, dissolved in butyl butyrate, and methanol was removed by solvent distillation to obtain the chain polymer binder solution.

[0480] Thus, a chain polymer (a random copolymer of (meth)acrylic acid polymer) SA-1, which forms the binder polymer P3, was synthesized, and a solution SA-1 (concentration 10% by mass) of the chain polymer binder PB3 composed of this polymer was obtained. The mass-average molecular weight of the obtained chain polymer P3 was 400,000, and the tensile permanent deformation could not be determined (by the method described below).

[0481] [Synthesis example SA-2]

[0482] In Synthesis Example SA-1, 28.6 g of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.2 g of maleic anhydride (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 7.2 g of tert-butyl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation) were used as monomers. Otherwise, a chain polymer (a random copolymer of (meth)acrylic acid polymer) SA-2 was synthesized in the same manner as in Synthesis Example SA-1, yielding a chain polymer binder solution SA-2 (concentration 10% by mass) composed of this polymer. The obtained chain polymer had a mass-average molecular weight of 360,000, and its tensile permanent deformation could not be determined (by the method described below).

[0483] [Synthesis example SA-3]

[0484] In Synthesis Example SA-1, 30.4 g of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.2 g of maleic anhydride (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 5.4 g of N-tert-butylacrylamide (manufactured by FUJIFILM Wako Pure Chemical Corporation) were used as monomers. Otherwise, a chain polymer (a random copolymer of (meth)acrylic acid polymer) SA-3 was synthesized in the same manner as in Synthesis Example SA-1, yielding a chain polymer binder solution SA-3 (concentration 10% by mass) composed of this polymer. The obtained chain polymer had a mass-average molecular weight of 380,000, and its tensile permanent deformation could not be determined (by the method described below).

[0485] [Synthesis example SA-4]

[0486] In Synthesis Example SA-1, 30.4 g of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.2 g of maleic anhydride (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 5.4 g of N-methylmethacrylamide (manufactured by Tokyo Chemical Industry Co., Ltd.) were used as monomers. Otherwise, a chain polymer (a random copolymer of (meth)acrylic acid polymer) SA-4 was synthesized in the same manner as in Synthesis Example SA-1, yielding a chain polymer binder solution SA-4 (concentration 10% by mass) composed of this polymer. The obtained chain polymer had a mass-average molecular weight of 420,000, and its tensile permanent deformation could not be determined (by the method described below).

[0487] [Synthesis example SA-5]

[0488] In Synthesis Example SA-1, 28.6 g of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.2 g of maleic anhydride (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 7.2 g of cyclohexyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) were used as monomers. Otherwise, a chain polymer (a random copolymer of (meth)acrylic acid polymer) SA-5 was synthesized in the same manner as in Synthesis Example SA-1, yielding a chain polymer binder solution SA-5 (concentration 10% by mass) composed of this polymer. The obtained chain polymer had a mass-average molecular weight of 390,000, and its tensile permanent deformation could not be determined (by the method described below).

[0489] The following shows the synthesized polymers. The numbers listed in the lower right corner of each component indicate its content (mass %). The polymers S-2 to S-5 have different component contents than polymer S-1, but otherwise have the same components; therefore, their chemical formulas are omitted. The chemical formulas for polymers T-1 to T-3 are also omitted.

[0490] Furthermore, in the chemical formulas of the following polymers, when the blocks are designated as A and B, "A-block-B" indicates a nomenclature based on the copolymer's raw material base, and "-block-" indicates a block polymer composed of blocks of component A and blocks of component B. In the following chemical formulas, Me represents methyl, and nBu represents n-butyl.

[0491] [Chemical Formula 2]

[0492]

[0493] [Chemical Formula 3]

[0494]

[0495] [Chemical Formula 4]

[0496]

[0497] [Chemical Formula 5]

[0498]

[0499] Table 1 shows the bonding mode, tensile set, elongation at break, and mass-average molecular weight of each synthesized polymer segment. Tensile set and elongation at break are expressed as determined by the methods described below, and mass-average molecular weight is calculated according to the methods described above. Furthermore, the glass transition temperature (denoted as "Tg" in Table 1) of the compounds incorporating the constituent components was determined by the methods described above, and the results are shown below or in Table 1.

[0500] In addition, polymers S-15, T-2 and T-3 are random polymers, and since the glass transition temperature of each block cannot be determined, they are indicated by "-" in Table 1.

[0501] Furthermore, polymer T-2 exhibits strong film adhesion at room temperature, making it unsuitable for fabricating self-supporting films. Consequently, polymer T-5 is also unsuitable for fabricating self-supporting films at room temperature (due to breakage upon cutting). Therefore, it is impossible to determine tensile permanent deformation and elongation at break. These are indicated by "-" in Table 1.

[0502] Polymer T-1 is polyurethane, therefore the bonding mode column is indicated by "-".

[0503] -Determination of tensile permanent deformation-

[0504] The tensile permanent deformation of the polymer was measured as follows.

[0505] Specifically, 2 cc of a polymer solution or dispersion (10% by mass solids) was coated onto a Teflon (registered trademark) sheet and dried at 120°C for 6 hours to obtain a dried film with a thickness of approximately 150 μm. The obtained film was cut into strips 10 mm wide and 40 mm long, and a force gauge (IMADA) with a clamping distance of 30 mm was used. The film was stretched at a speed of 10 mm / min until the target elongation reached 100% (i.e., 200% of the total length after stretching), and then immediately returned to the original clamping position at the same speed (one stretching and recovery cycle). The displacement and load at this point were measured, a stress-strain curve was plotted, and the permanent tensile deformation was calculated using the following formula.

[0506] Permanent tensile deformation (%) = (L S / L0)×100

[0507] ={1-((L1 / L0)×100}

[0508] In the above formula, such as Figure 3 As shown, L S L0 represents the displacement after recovery (mm), L1 represents the displacement after stretching (length at elongation: 60mm), and L2 represents the difference between the displacement after stretching and the displacement after recovery (mm).

[0509] -Determination of Elongation at Break-

[0510] The elongation at break of the polymer was determined using the following method.

[0511] (Production of the experimental film)

[0512] 2cc of each synthesized polymer solution or dispersion (solid component concentration 10% by mass) was coated onto a Teflon (registered trademark) sheet and dried at 120°C for 6 hours to obtain a dried film with a thickness of 150μm. The obtained dried film was cut into strips 10mm wide and 40mm long to prepare test pieces.

[0513] (Determination of elongation at break)

[0514] Each prepared test piece was placed in a force gauge (manufactured by IMADA) with the clamp spacing at 30 mm. Under these conditions, the test piece was stretched at a speed of 10 mm / min, and the displacement and stress were measured. The elongation at break was calculated from the displacement at fracture.

[0515]

[0516] <Abbreviation for table>

[0517] In the table, a "-" in the component column indicates that there is no corresponding component.

[0518] In Table 1, segment A is a segment containing constituent components derived from vinyl compounds or (meth)acrylate compounds with a glass transition temperature of 50°C or higher, and segment B is a segment containing constituent components derived from (meth)acrylate compounds with a glass transition temperature of 15°C or lower, preferably a segment whose overall glass transition temperature is 15°C or lower.

[0519] The following describes the compounds that are introduced as constituent components.

[0520] -Components M1 and M2-

[0521] Components M1 and M2 are the constituent components of chain segment A.

[0522] MMA: Methyl methacrylate (glass transition temperature of constituent components is 105°C)

[0523] IBOA: Isobornyl acrylate (glass transition temperature of the constituent component is 95°C)

[0524] AdA: Adamantyl acrylate (glass transition temperature of the constituent component is 150°C)

[0525] St: Styrene (glass transition temperature of its constituent components is 100°C)

[0526] tBA: tert-butyl acrylate (glass transition temperature of the constituent component is 40°C)

[0527] AA: Acrylic acid (glass transition temperature of constituent components is 106℃)

[0528] -Components M3~M5-

[0529] Constituents M3 to M5 are constituents of chain segment B. Constituents M4 and M5 are also constituents having functional groups selected from the functional group (a) described above.

[0530] BA: n-Butyl acrylate (glass transition temperature of the constituent component: -54℃)

[0531] EHA: 2-Ethylhexyl acrylate (glass transition temperature of constituent components: -50°C)

[0532] LA: Lauryl acrylate (glass transition temperature of the constituent component is -30°C)

[0533] H-BD: Butadiene hydride (glass transition temperature of constituent components -45°C)

[0534] BMA: n-Butyl methacrylate (glass transition temperature of the constituent component is 20°C)

[0535] HEA: Hydroxyethyl acrylate (glass transition temperature of constituent components: -45℃)

[0536] THFA: Tetrahydrofurfuryl acrylate (glass transition temperature of constituent components: -12°C)

[0537] MA: Maleic anhydride (a component that forms monomethyl esters).

[0538] AA: Acrylic acid (glass transition temperature of constituent components is 106℃)

[0539] In addition, the following components do not correspond to the above-mentioned components M1 to M5, but for convenience, they are shown in the respective component columns.

[0540] VDF: Vinylidene fluoride (glass transition temperature of constituent components: 35°C)

[0541] MDI: Diphenylmethane diisocyanate

[0542] HFP: Hexafluoropropylene

[0543] PTMG250: Polytetrahydrofuran (Number average molecular weight: 250)

[0544] TFE: Tetrafluoroethylene (glass transition temperature of constituent components is 126℃)

[0545] PEG200: Polyethylene glycol (number average molecular weight: 200, glass transition temperature of constituent components: -60℃)

[0546] GI1000: NISSO-PB GI-1000 (trade name, manufactured by Nippon Soda Co., Ltd., glass transition temperature of constituent components -44℃)

[0547] 4. Synthesis of sulfide-based inorganic solid electrolytes

[0548] [Synthesis Example A]

[0549] The sulfide-based inorganic solid electrolyte was synthesized with reference to the non-patent literature T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873.

[0550] Specifically, 2.42 g of lithium sulfide (Li₂S, manufactured by Aldrich, Inc., purity > 99.98%) and 3.90 g of phosphorus pentasulfide (P₂S₅, manufactured by Aldrich, Inc., purity > 99%) were weighed separately in a glove box under an argon atmosphere (dew point -70°C) and added to an agate mortar. The mixture was then mixed for 5 minutes using an agate pestle. The molar ratio of Li₂S to P₂S₅ was set as Li₂S:P₂S₅ = 75:25.

[0551] Next, 66g of 5mm diameter zirconia beads were added to a 45mL zirconia container (manufactured by Fritsch Co., Ltd.), along with the total amount of the aforementioned mixture of lithium sulfide and phosphorus pentasulfide. The container was then completely sealed under argon atmosphere. The container was placed in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.) and mechanically ground at 25°C and 510 rpm for 20 hours to obtain 6.20g of a yellow powder-like sulfide-based inorganic solid electrolyte (Li-PS glass, hereinafter, sometimes labeled LPS). The average particle size of the Li-PS glass was 15μm.

[0552] [Example 1]

[0553] The compositions shown in Tables 2-1 to 2-3 (collectively referred to as Table 2) were prepared as follows.

[0554] <Preparation of Inorganic Solid Electrolyte Compositions>

[0555] 60 g of 5 mm diameter zirconia beads were added to a 45 mL container (manufactured by Fritsch Japan Co., Ltd.). When using 8.4 g of LPS or LLT synthesized in Synthesis Example A above, 0.6 g (solid mass) or 0.3 g (solid mass) of the binder solution or dispersion shown in Table 2-1, or 0.3 g of binder solution, 0.3 g (solid mass) of the particulate binder dispersion Lx-1 or chain polymer binder solutions SA-1 to SA-5 shown in Table 2-1, and 11 g of the dispersion medium shown in Table 2-1 were further added. The container was then placed in a Fritsch Co., Ltd. planetary ball mill P-7 (trade name). Mixing was performed at 25°C and 150 rpm for 10 minutes to prepare inorganic solid electrolyte compositions (slurries) K-1 to K-24, K-27 to K-30, and Kc1 to Kc5, respectively.

[0556] Furthermore, in the preparation of inorganic solid electrolyte composition K-24, the contents (mixing amount) of binder solution S-4 and chain polymer binder solution SA-1 were changed to the contents shown in Table 2-1 (the total mass of solid components is 0.6g). Otherwise, inorganic solid electrolyte compositions K-25 and K-26 were prepared in the same manner as the preparation of inorganic solid electrolyte composition K-24.

[0557] <Preparation of the positive electrode composition>

[0558] 60 g of 5 mm diameter zirconia beads were added to a 45 mL zirconium oxide container (made by Fritsch Co., Ltd.), along with 8 g of LPS synthesized in Synthesis Example A and 13 g of the dispersion medium shown in Table 2-2 (total). The container was placed in a Fritsch Co., Ltd. planetary ball mill P-7 (trade name) and stirred at 25 °C and 200 rpm for 30 minutes. Subsequently, 27.5g of NMC (manufactured by Sigma-Aldrich Co. LLC) as the positive electrode active material, 1.0g of acetylene black (AB) as the conductive additive, 0.5g (solid component mass) or 0.25g (solid component mass) of the binder solution shown in Table 2-2 were added to the container. When using 0.25g of binder solution or dispersion, 0.25g (solid component mass) of the particulate binder dispersion Lx-1 or chain polymer binder solutions SA-1 to SA-5 shown in Table 2-2 were further added. The container was placed in a planetary ball mill P-7 and mixed for 30 minutes at a temperature of 25°C and a speed of 200 rpm to prepare positive electrode compositions (slurries) PK-1 to PK-23 and PK-26 to PK-29, respectively.

[0559] Furthermore, in the preparation of the positive electrode composition PK-23, the contents (mixing amount) of the binder solution S-4 and the chain polymer binder solution SA-1 were changed to the contents shown in Table 2-2 (the total mass of solid components is 0.5g). Otherwise, positive electrode compositions PK-24 and PK-25 were prepared in the same manner as the preparation of positive electrode composition PK-23.

[0560] <Preparation of the negative electrode composition>

[0561] 60 g of 5 mm diameter zirconia beads were added to a 45 mL container (manufactured by Fritsch Japan Co., Ltd). When using 8.0 g of LPS synthesized in Synthesis Example A, 0.4 g (solid mass) or 0.2 g (solid mass) of the binder solution or dispersion shown in Table 2-3, and 0.2 g of binder solution, 0.2 g (solid mass) of the particulate binder dispersion Lx-1 or chain polymer binder solutions SA-1 to SA-5 shown in Table 2, and 17.5 g (total) of the dispersion medium shown in Table 2-3 were further added. The container was placed in a Fritsch Co., Ltd. planetary ball mill P-7 (trade name) and mixed for 60 minutes at 25°C and 300 rpm. Then, 9.5g of the active material shown in Table 2-3 and 1.0g of VGCF (made by SHOWA DENKO KK) as a conductive additive were added. Similarly, the container was placed in a planetary ball mill P-7 and mixed for 10 minutes at a temperature of 25°C and a speed of 100 rpm to prepare negative electrode compositions (slurries) NK-1~NK-24, NK-27~NK-30 and NKc1~NKc5 respectively.

[0562] Furthermore, in the preparation of the negative electrode composition NK-24, the contents (mixing amount) of the binder solution S-4 and the chain polymer binder solution SA-1 were changed to the contents shown in Table 2-3 (the total mass of solid components is 0.4g). Otherwise, negative electrode compositions NK-25 and NK-26 were prepared in the same manner as the preparation of negative electrode composition NK-24.

[0563] -Determination of Adsorption Rate-

[0564] The adsorption rate A of the binder for the inorganic solid electrolyte was determined using the inorganic solid electrolyte, polymer binder, and dispersion medium used to prepare the compositions shown in Table 2. SE The results are shown in Table 2.

[0565] Specifically, a 1% (w / w) polymer binder solution or dispersion was prepared by dissolving the polymer binder in a dispersion medium. The polymer binder solution or dispersion and the inorganic solid electrolyte were placed in a 15 mL vial at a mass ratio of 35:1. The mixture was stirred for 1 hour at 80 rpm at room temperature using a mixing rotor and then allowed to stand. The supernatant obtained after solid-liquid separation was filtered through a 1 μm filter. The filtrate was completely dried, and the mass of the polymer binder remaining in the filtrate (the mass of the polymer binder not adsorbed onto the inorganic solid electrolyte) W was determined. A The mass W A and the mass W of the adhesive contained in the adhesive solution used for the testB The adsorption rate of the polymer binder for the inorganic solid electrolyte can be calculated using the following formula.

[0566] Adsorption rate A of polymer adhesive SE Let denoted as the average adsorption rate obtained by performing the above measurement twice.

[0567] Adsorption rate (%) = [(W)] B -W A ) / W B ]×100

[0568] In addition, the adsorption rate A was determined using inorganic solid electrolytes and polymer binders extracted from the solid electrolyte layer formed into a film, and the dispersion medium used to prepare the composition containing inorganic solid electrolytes. SE The result was the same.

[0569] In Table 2, the composition content is the content (mass%) relative to the total mass of the composition, and the solid component content is the content (mass%) relative to 100% mass of the solid component of the composition. Units are omitted in the table.

[0570] The “State” column in Table 2 indicates the state of the polymer binder in each composition. The state in which the polymer binder is dissolved in the dispersion medium is marked as “dissolved”, and the state in which the polymer binder is not dissolved in the dispersion medium but dispersed in particulate form is marked as “particulate”.

[0571] Additionally, in Table 2, when using the polymer adhesive PB1 and particulate adhesive PB2 or chain polymer adhesive PB3 as specified in this invention, the content of each "content", "A" is as follows: SE In the “Status” column, use “ / ” to record the value or status of each adhesive.

[0572]

[0573]

[0574]

[0575] <Abbreviation for table>

[0576] LPS: LPS synthesized in Synthesis Example A

[0577] LLT: Li 0.33 La 0.55 TiO3 (average particle size 3.25 μm, manufactured by Toshima Manufacturing Co., Ltd.)

[0578] NMC: LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2

[0579] Si: Silicon (Si, manufactured by Aldrich)

[0580] Graphite: Graphite (manufactured by Aldrich)

[0581] AB: Acetylene Black

[0582] VGCF: Carbon nanotubes (made by SHOWA DENKO KK)

[0583] <Fabrication of Solid Electrolyte Sheets for All-Solid-State Secondary Batteries>

[0584] Using a baking applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), the inorganic solid electrolyte compositions shown in the "Composition No." column of Table 3-1 obtained above were coated onto aluminum foil with a thickness of 20 μm. The coatings were heated at 80°C for 2 hours and then dried (to remove the dispersion medium). Then, using a hot press, the dried inorganic solid electrolyte compositions were heated and pressurized for 10 seconds at 120°C and 40 MPa to produce solid electrolyte sheets (marked as solid electrolyte sheets in Table 3-1) 101–122, 166–169, 178–181, and c11–c15 for all-solid-state secondary batteries. The film thickness of the solid electrolyte layer was 50 μm.

[0585] <Fabrication of Positive Electrode Sheets for All-Solid-State Secondary Batteries>

[0586] Using a baking applicator (trade name: SA-201), the positive electrode compositions shown in the "Composition No." column of Table 3-2 obtained above were coated onto aluminum foil with a thickness of 20 μm. The coatings were heated at 80°C for 1 hour, then further heated at 110°C for 1 hour, and dried (to remove the dispersion medium). Then, using a hot press, the dried positive electrode compositions were pressurized at 25°C (10 MPa, 1 minute) to produce positive electrode sheets (labeled as positive electrode sheets in Table 3-2) 123–143, 170–173, and 182–185 for all-solid-state secondary batteries, each with a positive electrode active material layer with a film thickness of 80 μm.

[0587] <Fabrication of negative electrode sheets for all-solid-state secondary batteries>

[0588] Using a baking applicator (trade name: SA-201), the negative electrode compositions shown in the "Composition No." column of Table 3-3 obtained above were coated onto copper foil with a thickness of 20 μm. The coatings were heated at 80°C for 1 hour, then further heated at 110°C for 1 hour, and dried (to remove the dispersion medium). Then, using a hot press, the dried negative electrode compositions were pressurized at 25°C (10 MPa, 1 minute) to produce negative electrode sheets (labeled as negative electrode sheets in Table 3-3) 144–165, 174–177, 186–189, and c16–c20 for all-solid-state secondary batteries, each with a negative electrode active material layer with a film thickness of 70 μm.

[0589] <Evaluation 1: Dispersion Stability (Slurry Settling)>

[0590] Each prepared composition (slurry) was placed into a glass test tube with a diameter of 10 mm and a height of 4 cm until the height reached 4 cm, and allowed to stand at 25°C for 36 hours. The solid content ratio per 1 cm of slurry was calculated from the liquid level before and after standing. Specifically, immediately after standing, 1 cm of liquid was taken from the liquid surface and dried in an aluminum cup at 120°C for 2 hours. The mass of the solid content in the cup was measured, and the amount of each solid component before and after standing was calculated. The solid content ratio [WA / WB] of the solid content WA obtained after standing was calculated relative to the solid content WB before standing.

[0591] The ease of precipitation (precipitability) of the inorganic solid electrolyte was evaluated as a measure of the dispersion stability of the solid electrolyte composition, depending on which of the following evaluation criteria the solid component ratio was included in. In this test, the closer the solid component ratio was to 1, the better the dispersion stability, with an evaluation criterion of "D" or above considered acceptable. The results are shown in Tables 3-1 to 3-3 (collectively referred to as Table 3).

[0592] -Evaluation Criteria-

[0593] A: 0.9 ≤ solid content ratio ≤ 1.0

[0594] B: 0.7 ≤ solid content ratio < 0.9

[0595] C: 0.5 ≤ solid content ratio < 0.7

[0596] D: 0.3 ≤ solid content ratio < 0.5

[0597] E: 0.1 ≤ solid content ratio < 0.3

[0598] F: Solid content ratio < 0.1

[0599] <Evaluation 2: Operability>

[0600] A slurry with a solids content of 75% by mass was prepared by maintaining the same mixing ratio as the other compositions, except for the dispersion medium, but with a reduced amount of dispersion medium. A 2 mL polyethylene pipette (manufactured by Atect Corporation) was held vertically with the tip 10 mm below the slurry interface, and the slurry was aspirated at 25°C for 10 seconds. The mass W of the polyethylene pipette containing the aspirated slurry was measured. When the tare weight (self-weight) of the polyethylene pipette was set as W0, a slurry mass W - W0 less than 0.1 g was considered unabsorbable by the pipette. When the slurry could not be aspirated by the pipette, the upper limit of solids concentration that could be aspirated by the pipette while gradually adding dispersion medium was determined. The operability of the composition (whether it has an appropriate viscosity to form a flat and well-surfaced constituent layer) was evaluated based on which of the following evaluation criteria the obtained upper limit of solids concentration falls into. The solids concentration was calculated by placing 0.30 g of the prepared slurry on an aluminum cup and heating it at 120°C for 2 hours to distill off the dispersion medium.

[0601] In this experiment, a higher concentration of the above-mentioned upper limit solid components indicates better operability, with an evaluation standard of "D" or above considered acceptable. The results are shown in Table 3.

[0602] -Evaluation Criteria-

[0603] A: Upper limit for solid content concentration ≥ 70%

[0604] B: 70% > Upper limit of solid component concentration ≥ 60%

[0605] C: 60% > Upper limit of solid component concentration ≥ 50%

[0606] D: 50% > Upper limit of solid component concentration ≥ 40%

[0607] E: 40% > Upper limit of solid component concentration ≥ 30%

[0608] F: 30% > Upper limit of solid component concentration

[0609] <Evaluation 3: Fit>

[0610] The adhesion of solid particles in the solid electrolyte layer or active material layer of each sheet was evaluated, as well as the adhesion between the active material layer and the current collector.

[0611] Each sheet was cut into a rectangle 3cm wide x 14cm long. Using a cylindrical mandrel testing machine (product code 056, mandrel diameter 10mm, manufactured by Allgood), one end of the cut sheet was fixed in the machine along its length, and the central portion of the sheet was positioned to abut against the cylindrical mandrel. While stretching the other portion of the sheet along its length with a force of 5N, it was bent 180° along the circumference of the mandrel (with the mandrel as the axis). Furthermore, the solid electrolyte layer or active material layer of the sheet was placed on the side opposite to the mandrel (the substrate or current collector was placed on the mandrel side), and the width direction was set parallel to the axis of the mandrel. The test was conducted by gradually reducing the diameter of the mandrel from 32mm.

[0612] The evaluation is conducted under the following conditions: in the state of being wound on a mandrel and in the state of being unwound and restored to a sheet shape, the generation of defects (cracks, fissures, gaps, etc.) on the solid electrolyte layer or active material layer due to the adhesion and collapse of solid particles, and for the active material layer, the minimum diameter at which the peeling between the active material layer and the current collector cannot be confirmed by further measurement, and which of the following evaluation criteria this minimum diameter corresponds to.

[0613] In this test, the smaller the minimum diameter, the stronger the adhesion of the solid particles constituting the solid electrolyte layer or active material layer, and the stronger the adhesion between the active material layer and the current collector. Evaluation standard "D" or above is considered qualified.

[0614] -Evaluation Criteria-

[0615] A: Minimum diameter < 5mm

[0616] B: 5mm ≤ minimum diameter < 6mm

[0617] C: 6mm ≤ minimum diameter < 8mm

[0618] D: 8mm ≤ minimum diameter < 10mm

[0619] E: 10mm ≤ minimum diameter < 14mm

[0620] F: 14mm ≤ minimum diameter < 25mm

[0621] G: 25mm ≤ minimum diameter [Table 3-1]

[0622]

[0623] [Table 3-2]

[0624]

[0625] [Table 3-3]

[0626]

[0627] In Table 3, when using the polymer adhesive PB and particulate adhesive PB2 or chain polymer adhesive PB3 as specified in this invention, they are listed together in the "Adhesive solution, etc. No." column of Table 3 using " / ".

[0628] <Manufacturing of All-Solid-State Secondary Batteries>

[0629] First, an electrode sheet for an all-solid-state secondary battery with a solid electrolyte layer was fabricated as follows.

[0630] (Fabrication of positive electrode sheet for all-solid-state secondary batteries with solid electrolyte layer)

[0631] By having the solid electrolyte layer in contact with the positive electrode active material layer, the solid electrolyte sheet shown in the "Solid Electrolyte Layer (Sheet No.)" column of Table 4-1 was laminated onto the positive electrode active material layer of each all-solid-state secondary battery positive electrode sheet shown above. After being pressurized at 50 MPa at 25°C and transferred (laminated) using a press, the sheet was pressurized at 600 MPa at 25°C. Thus, all-solid-state secondary battery positive electrode sheets with a solid electrolyte layer of 30 μm thickness (positive electrode active material layer thickness of 60 μm) 123-143, 170-173 and 182-185 were respectively produced.

[0632] In addition, as shown in Table 4-1, two types (No. 113 and 122) of solid electrolyte layers 113 or 122 were fabricated as positive electrode sheets 135 for all-solid-state secondary batteries with solid electrolyte layers.

[0633] <Fabrication of negative electrode sheet for all-solid-state secondary batteries with solid electrolyte layer>

[0634] Next, with the solid electrolyte layer in contact with the negative electrode active material layer, the solid electrolyte sheets shown in the "Solid Electrolyte Layer (Sheet No.)" column of Table 4-2 were laminated onto the negative electrode active material layer of each all-solid-state secondary battery negative electrode sheet shown above. After being pressurized at 50 MPa at 25°C and transferred (laminated) using a press, they were pressurized at 600 MPa at 25°C. Thus, all-solid-state secondary battery negative electrode sheets with a solid electrolyte layer of 30 μm thickness (negative electrode active material layer thickness 50 μm) 144~165, 174~177, 186~189 and c16~c20 were produced respectively.

[0635] (Manufacturing of all-solid-state secondary batteries)

[0636] Next, the following was manufactured with Figure 1 The layered structure shown is an all-solid-state secondary battery.

[0637] 1. Manufacturing of the all-solid-state secondary battery No. 101

[0638] The positive electrode sheet No. 123 (aluminum foil with the solid electrolyte layer already peeled off) for an all-solid-state secondary battery with the aforementioned solid electrolyte layer is cut into circular plates with a diameter of 14.5 mm, and as shown in the figure. Figure 2 The assembly shown includes spacers and gaskets (in...) Figure 2 In a stainless steel 2032-type button battery case 11 (not shown), lithium foil cut into disc shapes with a diameter of 15 mm is layered on a solid electrolyte layer. After further layering stainless steel foil on top, the 2032-type button battery case 11 is riveted together, thereby manufacturing a [missing information - likely a battery type]. Figure 2 The all-solid-state secondary battery 13 shown is No. 101.

[0639] All-solid-state secondary batteries manufactured in this way have Figure 1 The layer structure shown (where the lithium foil corresponds to the negative electrode active material layer 2 and the negative electrode current collector 1).

[0640] 2. Manufacturing of all-solid-state secondary batteries No. 102-122, 145-148 and 153-156

[0641] In the manufacture of the aforementioned all-solid-state secondary battery No. 101, the all-solid-state secondary battery positive electrode sheet with a solid electrolyte layer, indicated by No. in the "Electrode Active Material Layer (Sheet No.)" column of Table 4-1, was used instead of the all-solid-state secondary battery positive electrode sheet No. 123 with a solid electrolyte layer. Otherwise, all-solid-state secondary batteries No. 102 to 122, 145 to 148 and 153 to 156 were manufactured in the same manner as the manufacture of all-solid-state secondary battery No. 101.

[0642] 3. Manufacturing of All-Solid-State Secondary Battery No. 123

[0643] The negative electrode sheet No. 144 (aluminum foil with the solid electrolyte sheet already peeled off) of each all-solid-state secondary battery with the solid electrolyte obtained above is cut into circular plates with a diameter of 14.5 mm, and as follows: Figure 2 The assembly shown includes spacers and gaskets (in...) Figure 2In a stainless steel 2032-type button cell battery case 11 (not shown), a positive electrode sheet (positive active material layer) cut to a diameter of 14.0 mm from the positive electrode sheet for all-solid-state secondary batteries (prepared as described below) is stacked on a solid electrolyte layer. A stainless steel foil (positive current collector) is then stacked on top to form an all-solid-state secondary battery laminate 12 (a laminate composed of stainless steel foil, aluminum foil, positive active material layer, solid electrolyte layer, negative active material layer, and copper foil). The 2032-type button cell battery case 11 is then pressed together, thereby manufacturing a... Figure 2 The all-solid-state secondary battery shown is No. 123.

[0644] The following is a positive electrode sheet for manufacturing all-solid-state secondary batteries, specifically the No. 123 all-solid-state secondary battery.

[0645] (Preparation of the positive electrode composition)

[0646] 180 zirconia beads with a diameter of 5 mm were added to a 45 mL zirconium oxide container (manufactured by Fritsch Co., Ltd.), along with 2.7 g of LPS synthesized in Synthesis Example A above, 0.3 g of KYNAR FLEX 2500-20 (trade name, PVdF-HFP: polyvinylidene fluoride hexafluoropropylene copolymer, manufactured by ARKEMA), and 22 g of butyl butyrate. The container was placed in a Fritsch Co., Ltd. planetary ball mill P-7 (trade name) and stirred at 25°C and 300 rpm for 60 minutes. Afterwards, 7.0 g of LiNi was added as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NMC) was assembled in the same manner in a planetary ball mill P-7 and mixed for 5 minutes at 25°C and 100 rpm to prepare positive electrode compositions.

[0647] (Fabrication of positive electrode sheet for solid secondary batteries)

[0648] The obtained positive electrode composition was coated onto a 20 μm thick aluminum foil (positive electrode current collector) using a baking applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.). The positive electrode composition was heated at 100°C for 2 hours and then dried (to remove the dispersion medium). Then, using a hot press, the dried positive electrode composition was pressurized at 25°C (10 MPa, 1 min) to produce a positive electrode sheet for all-solid-state secondary batteries with a positive electrode active material layer of 80 μm thickness.

[0649] 4. Manufacturing of all-solid-state secondary batteries No. 124~144, 149~152, 157~160 and C101~C105

[0650] In the production of the all-solid secondary battery No. 123 described above, all-solid secondary battery negative electrode sheets with a solid electrolyte layer indicated by the Nos. shown in the "Electrode Active Material Layer (Sheet No.)" column of Table 4 were used in place of the all-solid secondary battery negative electrode sheet No. 144 having a solid electrolyte layer, and except for this, all-solid secondary batteries Nos. 124 to 144, 149 to 152, 157 to 160, and c101 to c105 were respectively produced in the same manner as in the production of all-solid secondary battery No. 123.

[0651] <Evaluation 4: Measurement of Ionic Conductivity>

[0652] The ionic conductivity of each of the produced all-solid secondary batteries was measured. Specifically, for each all-solid secondary battery, in a constant temperature bath at 30°C, using a 1255B FREQUENCY RESPONSE ANALYZER (trade name, manufactured by SOLARTRON), AC impedance was measured up to a voltage amplitude of 5 mV and a frequency of 1 MHz to 1 Hz. From this, the resistance in the layer thickness direction of the sample for ionic conductivity measurement was determined, and the ionic conductivity was calculated and obtained by the following formula (1).

[0653] Formula (1): Ionic conductivity σ (mS / cm) =

[0654] 1000 × Sample layer thickness (cm) / [Resistance (Ω) × Sample area (cm 2 )]

[0655] In formula (1), the sample layer thickness is a value obtained by measurement before placing the laminate 12 into the 2032-type coin case 11 and subtracting the thickness of the current collector (total layer thickness of the solid electrolyte layer and the electrode active material layer). The sample area is the area of a disk-shaped sheet with a diameter of 14.5 mm.

[0656] It was determined which of the following evaluation criteria the obtained ionic conductivity σ falls into.

[0657] Among the ionic conductivity σ in this experiment, an evaluation criterion of "C" or higher is regarded as passing.

[0658] -Evaluation Criteria-

[0659] A: 0.60≤σ

[0660] B: 0.50≤σ<0.60

[0661] C: 0.40≤σ<0.50

[0662] D: 0.30≤σ<0.40

[0663] E: 0.20 ≤ σ < 0.30

[0664] F: σ < 0.20

[0665] <Evaluation 5: Cyclic Characteristics (Discharge Capacity Retention) Test>

[0666] For each of the manufactured all-solid-state secondary batteries, the discharge capacity retention was measured using the TOSCAT-3000 charge-discharge evaluation device (trade name, manufactured by TOYO SYSTEM Co., Ltd.).

[0667] Specifically, each all-solid-state secondary battery was charged at 30°C until the current density reached 0.1 mA / cm². 2 And continue discharging until the battery voltage reaches 3.6V. Then, discharge until the current density reaches 0.1mA / cm². 2 The battery voltage was maintained at 2.5V. One charge and one discharge cycle was considered one charge-discharge cycle, and this process was repeated for three cycles under the same conditions to initialize the battery. Then, a current density of 3.0 mA / cm² was applied. 2 Charge until the battery voltage reaches 3.6V, at a current density of 3.0mA / cm². 2 A high-speed charge-discharge cycle, consisting of discharging until the battery voltage reaches 2.5V, was defined as one cycle. This high-speed charge-discharge cycle was repeated 500 times. The discharge capacity of each all-solid-state secondary battery in the first high-speed charge-discharge cycle and the discharge capacity in the 500th high-speed charge-discharge cycle were measured using a charge-discharge evaluation device: TOSCAT-3000 (trade name). The discharge capacity retention rate was calculated using the following formula, and this discharge capacity retention rate was applied to the following evaluation criteria to evaluate the cycle characteristics of the all-solid-state secondary batteries. In this test, a rating of "C" or above was considered acceptable. The results are shown in Table 4.

[0668] Discharge capacity retention (%) = (Discharge capacity in the 500th cycle / Discharge capacity in the 1st cycle) × 100

[0669] In this experiment, the higher the evaluation standard, the better the battery performance (cycle characteristics), and the better the battery performance can be maintained even after repeated high-speed charge and discharge cycles (even after long-term use).

[0670] Furthermore, the discharge capacity of the all-solid-state secondary battery used for evaluation in this invention consistently showed values ​​sufficient for the all-solid-state secondary battery to function effectively. Moreover, even without the aforementioned high-speed charge-discharge cycle, but under the same initialization conditions as described above, the all-solid-state secondary battery used for evaluation in this invention maintained excellent cycle characteristics.

[0671] -Evaluation Criteria-

[0672] A: 90% ≤ Discharge Capacity Maintenance Rate

[0673] B: 85% ≤ Discharge Capacity Retention < 90%

[0674] C: 80% ≤ Discharge capacity retention < 85%

[0675] D: 75% ≤ Discharge Capacity Retention < 80%

[0676] E: 70% ≤ Discharge capacity retention < 75%

[0677] F: 60% ≤ Discharge capacity retention < 70%

[0678] G: Discharge capacity retention < 60% [Table 4-1]

[0679]

[0680] [Table 4-2]

[0681]

[0682] The following information can be obtained from the results shown in Tables 3 and 4.

[0683] The inorganic solid electrolyte compositions containing polymer binders T-1, T-4, and T-5 exhibit poor dispersion stability and operability. The solid particles in the constituent layer formed using the negative electrode compositions containing these polymer binders have insufficient adhesion. Therefore, all-solid-state secondary batteries with constituent layers made using compositions containing polymer binders T-1, T-4, and T-5 do not exhibit sufficient ionic conductivity and cycle characteristics. Furthermore, while the inorganic solid electrolyte compositions containing polymer binders T-2 and T-3, which include random polymers, have satisfactory dispersion stability and operability, the solid particles in the constituent layer formed using the negative electrode compositions containing these polymer binders have insufficient adhesion. Therefore, all-solid-state secondary batteries with constituent layers made using these compositions do not exhibit sufficient ionic conductivity and cycle characteristics.

[0684] In contrast, inorganic solid electrolyte compositions containing the polymer binder PB1 specified in this invention exhibit both high levels of dispersion stability and operability, and the solid particles in the constituent layers formed using these compositions are bonded together with sufficiently strong adhesion. Therefore, all-solid-state secondary batteries with constituent layers made using these compositions can achieve excellent cycle characteristics and high ionic conductivity.

[0685] Furthermore, when used in combination with polymer binder PB1 and chain polymer PB3, it can maintain strong adhesion while further improving dispersion stability and operability, enhancing the improvement effect on cycle characteristics, and achieving a higher level of balance between ionic conductivity and cycle characteristics.

[0686] The invention has been described together with its embodiments, but unless otherwise specified, the invention is not limited in any detail of the description and should be interpreted broadly without departing from the spirit and scope of the invention as shown in the claims.

[0687] This application claims priority based on Japanese Patent Application 2020-217232 filed on December 25, 2020, Japanese Patent Application 2021-017430 filed on February 5, 2021, and Japanese Patent Application 2021-185885 filed on November 15, 2021, which are incorporated herein by reference as part of the description herein.

[0688] Symbol Explanation

[0689] 1-Negative current collector, 2-Negative active material layer, 3-Solid electrolyte layer, 4-Positive active material layer, 5-Positive current collector, 6-Working part, 10-All-solid-state secondary battery, 11-Type 2032 button cell battery case, 12-Laminated body for all-solid-state secondary battery, 13-Button type all-solid-state secondary battery.

Claims

1. A composition containing an inorganic solid electrolyte, comprising: an inorganic solid electrolyte having conductive ions of metals belonging to Group 1 or Group 2 of the periodic table, a polymer binder PB, and a dispersion medium. in, The polymer binder PB comprises polymer binder PB1, which is formed from polymer P1 with a tensile permanent deformation of less than 50% in the stress-strain curve obtained by repeated stretching and recovery once, and the polymer binder PB1 has an adsorption rate of less than 60% for the inorganic solid electrolyte in the dispersion medium. The polymer P1 is a chain polymer and is selected from one or more of the group consisting of (meth)acrylic acid polymers, fluoropolymers and vinyl polymers.

2. The inorganic solid electrolyte composition according to claim 1, wherein, The permanent tensile deformation is less than 25%.

3. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The polymer P1 has an elongation at break of over 400%.

4. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The polymer P1 comprises a constituent having functional groups selected from the following functional group (a) Functional groups (a): Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, ether bond, imino, ester bond, amide bond, carbamate bond, thiocarbamate bond, urea bond, thiourea bond, heterocyclic group, aryl, carboxylic anhydride group, fluoroalkyl, siloxane, carbonate bond, ketone bond.

5. The inorganic solid electrolyte composition according to claim 4, wherein, The content of the constituent component in the polymer P1 is 0.1 to 20% by mass.

6. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The polymer P1 is a block polymer.

7. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The polymer P1 contains components derived from (meth)acrylate compounds.

8. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The polymer P1 is a block polymer having at least segment A and segment B, wherein segment A comprises constituents derived from vinyl compounds or (meth)acrylate compounds with a glass transition temperature of 50°C or higher, and segment B comprises constituents derived from (meth)acrylate compounds with a glass transition temperature of 15°C or lower.

9. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The polymer adhesive PB also includes a chain polymer adhesive PB3 composed of a (meth)acrylic acid polymer.

10. The inorganic solid electrolyte composition according to claim 1 or 2, wherein it contains an active substance.

11. The inorganic solid electrolyte composition according to claim 1 or 2, wherein it contains a conductive additive.

12. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The inorganic solid electrolyte is a sulfide-based inorganic solid electrolyte.

13. A sheet for an all-solid-state secondary battery, having a layer composed of an inorganic solid electrolyte composition as described in any one of claims 1 to 12.

14. An all-solid-state secondary battery, comprising sequentially a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein, At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer composed of an inorganic solid electrolyte composition as described in any one of claims 1 to 12.

15. A method for manufacturing a sheet for an all-solid-state secondary battery, wherein the inorganic solid electrolyte composition according to any one of claims 1 to 12 is used to form a film.

16. A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is manufactured by the manufacturing method of claim 15.

Citation Information

Patent Citations

  • Shift lever position indication method of and apparatus for automobile

    JP1981017725A

  • Latex agglutination reaction measuring instrument

    JP1987022066A

  • Catalyst carrier and production thereof

    JP1990006856A

  • Four-wheel steering device

    JP1991045473A

  • Distortion compensator

    JP1993090844A